Children's toy material prepared from plant starch and preparation method of children's toy material
Through the combination of plant starch and polylactic acid PLA, the modified grafting technology is used to solve the problem of non-degradable traditional petroleum-based plastic toys, and a safe, environmentally friendly, biodegradable children's toy materials are realized, meeting the GB6675-2014 standard, and Promote the utilization of agricultural resources.
Patent Information
- Application Number
- CN202411793163.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional petroleum-based plastic toys are non-degradable, resulting in environmental pollution and lack of safe and environmentally friendly alternative materials.
Using materials that combine plant starch and polylactic acid PLA, the modified grafting technology of corn starch compatibility and polylactic acid PLA compatibility is formed to form biodegradable children's toy materials, meeting the safety of Chinese children's toy standards GB6675-2014 Require.
It has achieved safe, environmentally friendly, biodegradable toy materials, reduced environmental pollution, met the environmental protection and safety standards of the toy industry, and promoted the diversified utilization of agricultural resources.
Smart Images

Figure CN119286069A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of toy manufacturing, and in particular to a children's toy material made from plant starch and a preparation method thereof. Background Art
[0002] Traditional petroleum-based plastic toys are non-degradable, and the environmental pollution caused by discarding them is becoming increasingly serious. As people's environmental awareness increases, environmental pollution issues have attracted much attention. Therefore, it is of great significance to develop a biodegradable, safe and environmentally friendly toy.
[0003] As an enterprise engaged in the toy manufacturing industry, we are not limited to general industry standards, but dare to innovate. Based on the Chinese children's toy standard GB6675-2014 "Toy Safety" national standard, we create safer and more environmentally friendly toy products. Plant starch comes from plants in nature. It is a natural substance with rich materials and relatively easy extraction. It does not produce harmful substances during production and use. It is environmentally friendly and is more easily biodegradable after being discarded, reducing pollution to the environment. Plant-based polylactic acid PLA tree refers to a polymer material obtained by chemical synthesis or biosynthesis with lactic acid as a monomer. Its raw materials are mainly corn, potatoes, etc., and its raw materials are natural crops. Lactic acid is non-toxic and non-irritating, biodegradable, and easily decomposed and metabolized by a variety of microorganisms in nature or enzymes in animals, eventually forming carbon dioxide and water, which reduces environmental pollution to a certain extent. It is an ideal safe and green material.
[0004] The use of environmentally friendly materials has penetrated into all areas of people's lives. In recent years, various industries have been enthusiastic about the research and development of new environmentally friendly products. Inspired by China's invention patents CN108948703A / CN116120724A, they have accelerated the development of a biodegradable children's toy. Summary of the invention
[0005] The purpose of the present invention is to solve the problems raised in the above background technology and to provide a material for manufacturing children's toys using plant starch, the performance of which meets the national standard of Chinese children's toys GB6675-2014 "Toy Safety".
[0006] In order to solve the above technical problems, the technical solution of the present invention is: a material for manufacturing children's toys from plant starch, characterized in that: its formula materials mainly include the following raw material components by weight percentage: 55-70% plant starch, 10-18% corn starch compatibilizer, 10-12% polylactic acid PLA, 10-15% polylactic acid PLA compatibilizer, 1-2% nucleating agent, 0.1-1% antioxidant, 0.5-2% antistatic agent, and 1-2% colorant; The plant starch is one or a mixture of corn starch, wheat starch, potato starch, rice starch and tapioca starch; The relative molecular weight range of the polylactic acid PLA is 1x10 5 -5x10 5 between; The nucleating agent is a polylactic acid stereocomplex SC, a polylactic acid PLLA / polylactic acid PDLA stereomer; The antioxidant is ascorbic acid vitamin C; The antistatic agent is a polyether antistatic agent, propylene glycol block polyether L64; The colorant is an organic colorant or a plant pigment. The organic pigment is one or more of phthalocyanine blue, phthalocyanine green, lemon yellow pigment, and pigment red 254. The plant pigment is one or more of zeaxanthin, curcumin, strawberry red pigment, and lycopene pigment.
[0007] In the above-mentioned plant starch for making children's toy materials, the corn starch compatibilizer is prepared by modified grafting of the reducing end of the terminal group of the corn starch molecular chain, and its raw material formula includes by weight percentage: 10kg corn starch, 0.5-1.0kg ascorbic acid vitamin C reducing agent, 2-5kg hydroxyethyl methacrylate monomer, 1-4kg itaconic acid monomer, and 0.1-0.5kg potassium persulfate initiator.
[0008] In the above-mentioned process of manufacturing children's toy materials with plant starch, the corn starch compatibilizer process steps are: (I) Reduction pretreatment of corn starch: (1) solution preparation, (2) reduction reaction; (ii) grafting reaction, (1) preparing a monomer mixture, (2) preparing an initiator solution, (3) grafting copolymerization reaction; (iii) Post-treatment: (1) product separation, (2) washing, and (3) drying.
[0009] In the above-mentioned plant starch for making children's toys, the PLA compatibilizer has a raw material formula by weight percentage: 100g PLA, 10-25g hydroxypropyl acrylate monomer, 10-25g ethyl lactate monomer, 1-5g potassium persulfate initiator, 150-250 mL ethyl acetate solvent, 10-25g propylene glycol additive; PLA molecular weight 1x10 5 -5x10 5As the basic materials of the main chain structure, hydroxypropyl acrylate monomer and ethyl lactate monomer can also be selected from one or more of hydroxyethyl methacrylate, itaconic acid, acrylic acid, polyethylene glycol, and maleic anhydride; the initiator can be selected from one or more of hydrogen peroxide, ammonium persulfate, lipase, laccase, tea polyphenols, and gallic acid; the solvent can be selected from one or more of ethyl lactate, polyethylene glycol, and propylene glycol; the auxiliary agent can be added according to the product performance requirements, and can be selected from one or more of nucleating agents such as talc powder, amide compounds, chain extenders such as epoxy functionalized chain extenders, and oxazoline type chain extenders; the plasticizer can be selected from one or more of citrate esters, polyethylene glycol, anti-hydrolysis agents such as carbodiimide anti-hydrolysis agents, and coupling agents such as silane coupling agents.
[0010] In the above-mentioned plant starch for manufacturing children's toy materials, the prepared polylactic acid PLA compatibilizer has the following process steps: (i) Raw material pretreatment: (1) dissolving polylactic acid, (2) mixing monomers and additives; (ii) Initiation reaction: (1) Preparation of initiator solution, (2) Grafting reaction; (iii) Post-processing: (1) solvent removal, (2) product purification.
[0011] The present invention also provides a method for manufacturing plant starch children's toys, which uses the plant starch to manufacture children's toy materials, and is characterized by comprising the following manufacturing process steps: 1. Raw material preparation: (1) Plant starch raw materials: pre-treat the plant starch by first drying the plant starch in an air flow dryer, then grinding the dried plant starch in a planetary ball mill, and screening the plant starch after grinding to ensure that the particles meet the standards; (2) Polylactic acid raw material: select polylactic acid (PLA) with appropriate molecular weight, pass the polylactic acid through a double-roll crusher, crush it, and then place it in a vacuum drying oven for drying; (II) Mixing process: (1) The pretreated plant starch and polylactic acid (PLA), corn starch compatibilizer, polylactic acid compatibilizer, nucleating agent, antioxidant, antistatic agent, and colorant are placed in a high-speed mixer according to weight percentage and mixed, and nitrogen is introduced into the mixer to prevent the materials from being oxidized during the mixing process; (2) After the mixing is completed, the premix is placed in a twin-screw extruder for blending and extrusion. The feeding section, solid conveying section, melting section, mixing section, exhaust section, and homogenization section of the extruder are set with a temperature gradient to ensure the physical reaction of the plant starch and polylactic acid PLA to be fully blended, forming a composite material extrusion, and directly transporting it to a thermoplastic machine for molding through a constant temperature pipeline, or cooling and pelletizing; (III) Molding process: (1) The extruded composite material is directly transported to the barrel of the injection molding, blow molding, and hot press through a constant temperature pipeline for plasticization, which can reduce the energy consumption of the melting process of the injection molding machine and reduce the change in material properties caused by the secondary melting of the granular material or the re-melting of the granules; (2) Sending the composite material to a molding machine for thermoplastic molding, and using corresponding molds for thermoplastic molding according to the design requirements of different toys; (IV) Post-processing process: (1) Annealing treatment: placing the formed toys in an annealing furnace for annealing treatment to improve the physical properties of the toys; (2) Painting: coating the surface of toys, printing and other decorative treatments on toys to increase their beauty and appeal; (3) Surface treatment: Use non-toxic, biodegradable natural plant rice bran wax to treat the surface of toys to improve the wear resistance, stain resistance and antibacterial properties of toys, further ensuring the safety of children's use.
[0012] In the above-mentioned method for manufacturing plant starch children's toys, in the raw material preparation, the plant starch is selected as corn starch, and the corn starch is placed in an air flow dryer and dried for 2-5 hours at a temperature of 50-60°C and an air flow velocity of 1.5-2.5m / s to reduce the moisture content of the corn starch to 0.5%-1%; then, the dried corn starch is placed in a planetary ball mill and ball-milled at a speed of 300-500r / min for 0.5-2 hours, and the corn starch after ball milling meets the 80-200 mesh standard after passing through a vibrating screen.
[0013] In the above-mentioned method for manufacturing plant starch children's toys, in the preparation of raw materials, polylactic acid PLA with a suitable molecular weight of 100,000-500,000 is selected. Before use, the polylactic acid is passed through a double-roll crusher to be crushed into smaller particles of 1-2 mm, placed in a vacuum drying oven, and dried for 3-5 hours at a temperature of 60-80°C and a vacuum degree of -0.08 to -0.1MPa to remove moisture and small molecular impurities therein.
[0014] In the above-mentioned method for manufacturing plant starch children's toys, in the mixing process, the stirring paddle speed of the high-speed mixer is set to 800-1200r / min, the mixing time is 10-30 minutes, and during the mixing process, nitrogen is introduced into the mixer with a nitrogen flow rate of 5-10L / min to prevent the material from being oxidized during the mixing process.
[0015] In the above-mentioned method for manufacturing plant starch children's toys, in the mixing process, the screw length-diameter ratio of the twin-screw extruder is 30:1-52:1, the screw speed is 100-200r / min, and the temperature setting of each section of the extruder is: the feeding section needs to have a large conveying capacity to ensure that the material can stably and continuously enter the screw, the temperature range is set at 100℃-130℃, the solid conveying section compacts the loose powdered material, and the fullness in the screw groove is prepared for the melting and plasticization of the material downstream, the temperature range is 120℃-140℃, and the exhaust port is set to reduce the gas content in the material. The melting section is the key stage for the material to transform from solid to liquid. Sufficient heat and shear force need to be provided to allow the plant starch and polylactic acid to be completely melted and mixed evenly. The temperature range is set at 150℃-180℃, and the corn starch and polylactic acid are fully mixed in the mixing section. Mix to form a uniform melt, and further reduce the size of the dispersed phase of the material to improve the mixing effect. The temperature range is 155℃-170℃. The exhaust section is mainly used to discharge moisture, entrained air and volatile components in the material so that the gas can be discharged smoothly. The temperature range is 140℃-160℃. The homogenization section makes the material at the die mouth have a certain density and further mixes it to achieve the purpose of smooth extrusion molding. The temperature range is 150℃-165℃. This temperature gradient setting ensures that the plant starch and polylactic acid PLA are fully blended and appropriate physical and chemical reactions occur to form a uniform composite material. Extrusion, cooling, and hot air drying obtain the plant starch composite material.
[0016] The present invention has the following beneficial effects: 1. The raw materials are taken from high molecular compound composite materials of crops such as corn, which are natural, safe and environmentally friendly.
[0017] 2. The auxiliary materials are safe and non-toxic organic materials, which can be touched and chewed by children, and are safe and risk-free.
[0018] 3. It can be biodegraded after disposal, which is conducive to the formation of a sustainable ecological cycle.
[0019] 4. Environmental protection: As it is biodegradable, it can reduce the pollution of toy waste to the environment, alleviate the pressure of social waste disposal, and help promote its implementation in the toy industry.
[0020] 5. Resource utilization, using crops as raw materials and promoting the diversified utilization of agricultural resources will help promote the extension of the agricultural industry chain.
[0021] 6. Healthy and safe, safe, non-toxic, non-irritating and chewable, it ensures the health of children during play and reduces the risk of disease caused by toy material problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1It is a process step for preparing corn starch compatibilizer; Figure 2 It is a process step for preparing polylactic acid PLA compatibilizer; Figure 3 The extruder has a 6-stage temperature gradient design; Figure 4 It is a process step in thermoplastic toy manufacturing. DETAILED DESCRIPTION
[0023] The present invention will be further described in conjunction with the accompanying drawings.
[0024] Please refer to Figures 1 to 4 , a material for making children's toys from plant starch, the formula of which mainly includes the following raw material components by weight percentage: 55-70% plant starch, 10-18% corn starch compatibilizer, 10-12% polylactic acid PLA, 10-15% polylactic acid PLA compatibilizer, 1-2% nucleating agent, 0.1-1% antioxidant, 0.5-2% antistatic agent, and 1-2% colorant; The plant starch is one or a mixture of corn starch, wheat starch, potato starch, rice starch, cassava starch, and other plant starch types with similar properties; The relative molecular weight range of the polylactic acid PLA is 1x10 5 -5x10 5 between; The nucleating agent is a polylactic acid stereocomplex SC, a polylactic acid PLLA / polylactic acid PDLA stereomer; The antioxidant is ascorbic acid vitamin C; The antistatic agent is a polyether antistatic agent, propylene glycol block polyether L64; The colorant is an organic colorant or a plant pigment. The organic pigment is one or more of phthalocyanine blue, phthalocyanine green, lemon yellow pigment, and pigment red 254. The plant pigment is one or more of zeaxanthin, curcumin, strawberry red pigment, and lycopene pigment.
[0025] Furthermore, the corn starch compatibilizer is prepared by modifying and grafting the reducing end of the end group of the corn starch molecular chain, and its raw material formula includes by weight percentage: 10kg corn starch, 0.5-1.0kg ascorbic acid vitamin C reducing agent, 2-5kg hydroxyethyl methacrylate monomer, 1-4kg itaconic acid monomer, 0.1-0.5kg potassium persulfate initiator. Other preparations with the same effect can also be selected, for example, reducing agents sodium bisulfite, ferrous sulfate, new type of hydrosulfite (sodium dithionite), monomers acrylic acid, methyl acrylate, butyl acrylate, glycidyl methacrylate, acrylamide, initiators ammonium persulfate, ammonium cerium nitrate, hydrogen peroxide.
[0026] Furthermore, the corn starch compatibilizer process steps are: (I) Reduction pretreatment of corn starch: (1) solution preparation, (2) reduction reaction; (ii) grafting reaction, (1) preparing a monomer mixture, (2) preparing an initiator solution, (3) grafting copolymerization reaction; (iii) Post-treatment: (1) product separation, (2) washing, and (3) drying.
[0027] Furthermore, the PLA compatibilizer has a raw material formula by weight percentage: 100g PLA, 10-25g hydroxypropyl acrylate monomer, 10-25g ethyl lactate monomer, 1-5g potassium persulfate initiator, 150-250 mL ethyl acetate solvent, 10-25g propylene glycol additive; PLA molecular weight 1x10 5 -5x10 5 As the basic materials of the main chain structure, hydroxypropyl acrylate monomer and ethyl lactate monomer can also be selected from one or more of hydroxyethyl methacrylate, itaconic acid, acrylic acid, polyethylene glycol, and maleic anhydride; the initiator can be selected from one or more of hydrogen peroxide, ammonium persulfate, lipase, laccase, tea polyphenols, and gallic acid; the solvent can be selected from one or more of ethyl lactate, polyethylene glycol, and propylene glycol; the auxiliary agent can be added according to the product performance requirements, and can be selected from one or more of nucleating agents such as talc powder, amide compounds, chain extenders such as epoxy functionalized chain extenders, and oxazoline type chain extenders; the plasticizer can be selected from one or more of citrate esters, polyethylene glycol, anti-hydrolysis agents such as carbodiimide anti-hydrolysis agents, and coupling agents such as silane coupling agents.
[0028] Further, the prepared polylactic acid PLA compatibilizer has the following process steps: (i) Raw material pretreatment: (1) dissolving polylactic acid, (2) mixing monomers and additives; (ii) Initiation reaction: (1) Preparation of initiator solution, (2) Grafting reaction; (iii) Post-processing: (1) solvent removal, (2) product purification.
[0029] The present invention also provides a method for manufacturing a plant starch children's toy using the plant starch as the material for the children's toy, which is characterized by comprising the following manufacturing process steps: 1. Raw material preparation: (1) Plant starch raw materials: pre-treat the plant starch by first drying the plant starch in an air flow dryer, then grinding the dried plant starch in a planetary ball mill, and screening the plant starch after grinding to ensure that the particles meet the standards; (2) Polylactic acid raw material: select polylactic acid (PLA) with appropriate molecular weight, pass the polylactic acid through a double-roll crusher, crush it, and then place it in a vacuum drying oven for drying; (II) Mixing process: (1) The pretreated plant starch and polylactic acid (PLA), corn starch compatibilizer, polylactic acid compatibilizer, nucleating agent, antioxidant, antistatic agent, and colorant are placed in a high-speed mixer according to weight percentage and mixed, and nitrogen is introduced into the mixer to prevent the materials from being oxidized during the mixing process; (2) After mixing, the premix is placed in a twin-screw extruder for blending and extrusion. The temperature gradient of the extruder's feeding section, solid conveying section, melting section, mixing section, exhaust section, and homogenization section is set to ensure the physical reaction of the plant starch and polylactic acid PLA to be fully blended, forming a composite material extrusion, and directly transporting it to the thermoplastic machine for molding through a constant temperature pipeline, or cooling and pelletizing; (III) Molding process: (1) The extruded composite material is directly transported to the barrel of the injection molding, blow molding, and hot press through a constant temperature pipeline for plasticization, which can reduce the energy consumption of the melting process of the injection molding machine and reduce the change in material properties caused by the secondary melting of the granular material or the re-melting of the granules; (2) Sending the composite material to a molding machine for thermoplastic molding, and using corresponding molds for thermoplastic molding according to the design requirements of different toys; (IV) Post-processing process: (1) Annealing treatment: placing the formed toys in an annealing furnace for annealing treatment to improve the physical properties of the toys; (2) Painting: coating the surface of toys, printing and other decorative treatments on toys to increase their beauty and appeal; (3) Surface treatment: Use non-toxic, biodegradable natural plant rice bran wax to treat the surface of toys to improve the wear resistance, stain resistance and antibacterial properties of toys, further ensuring the safety of children's use.
[0030] Furthermore, the plant starch is selected as corn starch, and the corn starch is placed in an air flow dryer and dried for 2-5 hours at a temperature of 50-60°C and an air flow velocity of 1.5-2.5m / s to reduce the water content of the corn starch to 0.5%-1%; then, the dried corn starch is placed in a planetary ball mill and ball-milled at a speed of 300-500r / min for 0.5-2 hours, and the corn starch after ball milling meets the 80-200 mesh standard after passing through a vibrating screen.
[0031] Furthermore, in the preparation of raw materials, polylactic acid PLA with a suitable molecular weight of 100,000-500,000 is selected. Before use, the polylactic acid is crushed into 1-2 mm smaller particles by a double-roll crusher, placed in a vacuum drying oven, and dried for 3-5 hours at a temperature of 60-80°C and a vacuum degree of -0.08 to -0.1MPa to remove moisture and small molecular impurities therein.
[0032] Furthermore, in the raw material preparation, in the mixing process, the stirring blade speed of the high-speed mixer is set to 800-1200r / min, the mixing time is 10-30 minutes, and during the mixing process, nitrogen is introduced into the mixer at a nitrogen flow rate of 5-10L / min to prevent the material from being oxidized during the mixing process.
[0033] Furthermore, in the raw material preparation and mixing process, the screw length-diameter ratio of the twin-screw extruder is 30:1-52:1, the screw speed is 100-200r / min, and the temperature settings of each section of the extruder are: the feeding section needs to have a large conveying capacity to ensure that the material can stably and continuously enter the screw, and the temperature range is set at 100℃-130℃. The solid conveying section compacts the loose powdered material and fills the screw groove to prepare for the melting and plasticization of the material downstream. The temperature range is 120℃-140℃, and the exhaust port is set to reduce the gas content in the material. The melting section is the key stage for the material to transform from solid to liquid. Sufficient heat and shear force need to be provided to allow the plant starch and polylactic acid to be completely melted and mixed evenly. The temperature range is set at 150℃-180℃. The mixing section is the stage where corn starch and polylactic acid are fully Mix to form a uniform melt, and further reduce the size of the dispersed phase of the material to improve the mixing effect. The temperature range is 155℃-170℃. The exhaust section is mainly used to discharge moisture, entrained air and volatile components in the material so that the gas can be discharged smoothly. The temperature range is 140℃-160℃. The homogenization section makes the material at the die mouth have a certain density and further mixes it to achieve the purpose of smooth extrusion molding. The temperature range is 150℃-165℃. This temperature gradient setting ensures that the plant starch and polylactic acid PLA are fully blended and appropriate physical and chemical reactions occur to form a uniform composite material. Extrusion, cooling, and hot air drying obtain the plant starch composite material.
[0034] The present invention is further described in detail below: Plant starch is a high molecular compound. As the raw material for making children's toys, the material selection basis and technical solution explanation require the basic knowledge of the molecular chain structure, aggregation structure, physical properties and chemical properties of plant starch.
[0035] The main components of plant starch such as corn starch, wheat starch, potato starch, rice starch, and cassava starch are all polysaccharides, which are composed of multiple glucose molecules connected by glycosidic bonds. Their chemical structures are natural high molecular compounds with large relative molecular mass. The end groups of starch all have a reducing end and a non-reducing end. The reducing end has potential reducing properties and can react with some oxidants. The non-reducing end is relatively stable in chemical reactions. The reducing end can participate in oxidation reactions and react with oxidants. It can be oxidized into carboxyl groups by weak oxidants and participate in graft copolymerization reactions. The reducing end can serve as an initiation point to initiate graft copolymerization reactions between starch and other monomers. Under the action of the initiator, the reducing end generates free radicals, which then react with the monomers to form graft copolymers to give starch new functions and improve its water resistance, heat resistance, and mechanical properties. The non-reducing end provides a reaction site. Through chemical modification, specific functional groups can be introduced into the non-reducing end, thereby changing the properties of starch. In the esterification reaction of starch, ester groups can be introduced into the non-reducing end to improve the properties of starch. In the esterification reaction of starch, ester groups can be introduced into the non-reducing end to improve the hydrophobicity and thermoplasticity of starch. According to the chemical structure of starch, scientifically select additives and processes to enhance compatibility with other materials.
[0036] The molecular chains of starch have similar structures and the same basic components. They are all composed of glucose molecules connected by a-1,4-glycosidic bonds and a-1,6-glycosidic bonds. They all have a certain branching structure and are composed of straight-chain starch and amylopectin. The branching degree of amylopectin is relatively high. By controlling the length and branching degree of the molecular chain, the strength, hardness and toughness of the material can be adjusted. The molecular chain structure can also affect the degradation performance of the material. The degradation rate of biodegradable toy materials can be controlled by adjusting the molecular chain structure.
[0037] The aggregated structure of starch exists in the form of granules. These starches usually aggregate in the form of granules in the natural state. There is a certain ordered structure inside the granules, which has a certain degree of crystallinity. There are partial crystalline regions and amorphous regions inside the granules. The crystalline regions are mainly formed by the orderly arrangement of starch molecular chains. Optimizing the aggregated structure can improve the crystallinity of toy materials, thereby enhancing their mechanical properties and heat resistance.
[0038] Through experiments, it was found that when corn starch, wheat starch, potato starch, and rice starch are processed into thermoplastic starch materials by adding specific additives, shearing, mixing, and plasticizing at high temperatures, their chemical structure, molecular chain structure, and aggregation structure will change, meeting the requirements of thermoplastic molding toy materials.
[0039] The chemical structure of starch changes. After adding additives, high-temperature shearing, mixing and extrusion to become thermoplastic starch materials, the chemical structure will change, and some glycosidic bonds will break. Under the action of high temperature and shear force, the glycosidic bonds in the starch molecules will be damaged to a certain extent, resulting in shortening of the molecular chain, chemical reactions with additives, acetification, etherification and other reactions, the introduction of new chemical groups, and changes in the chemical properties of starch. It can improve compatibility with other substances and increase interfacial bonding.
[0040] The structure of starch molecular chains changes, molecular chains break and reorganize. High temperature and shear force can break starch molecular chains, and can also cause molecular chains to reorganize to form new molecular chain structures. The ratio of amylose to amylopectin changes. The processing process will affect the ratio of amylose to amylopectin. Amylose will be more susceptible to damage, resulting in a decrease in the ratio. The flexibility of the molecular chain changes. Due to the interaction with additives or the breakage and reorganization of the molecular chain, the flexibility of the molecular chain changes, thereby enhancing the hardness and toughness to achieve the mechanical properties required for making toys.
[0041] The aggregate structure of starch will change, and the particle structure will be destroyed. The high-temperature shear mixing process will destroy the original particle structure of starch, break the particles, form a new aggregate state, reduce crystallization, and increase the amorphous area. With the destruction of the crystalline structure, the amorphous area will increase relatively, the disorder of the material will be enhanced, and a new phase will be formed. Under the action of additives, a new phase will be formed to form a blended phase or a new composite phase with the additives; thereby improving the thermal stability of toy materials suitable for the processing temperature range, and selecting the appropriate molding method according to the structure of the aggregate state, such as blow molding or injection molding.
[0042] After adding additives, and processing starch into mature plastic starch materials through high-temperature shearing, mixing and plasticization, its chemical properties will change. After adding additives, chemical reactions or interactions will occur between starch molecules and additives, thereby changing the chemical activity of the material, making it easier to compound or modify with other materials, and enhancing water resistance. By adding specific additives, thermoplastic starch materials can improve their resistance to moisture and reduce water absorption, thereby extending the service life of the material. Degradability and degradation rate will change. The degradability of thermoplastic starch materials depends on the additives and process conditions used in the processing process. By adjusting the process to control the material's degradation rate, different application scenarios of toys can be met.
[0043] After starch is processed into thermoplastic materials by adding additives and high-temperature shearing, mixing and plasticizing, its physical properties will change. The starch, which was originally a white powder in appearance, will become solid material particles with a certain shape. The mechanical properties and strength will increase. After processing, the tensile strength, bending and other mechanical properties of the material will be improved, and it will have better tensile and bending resistance. The toughness will be improved, making it more resilient and not easy to break. The solubility and dispersibility of the thermoplastic material in water will change after processing, and it needs to be dissolved under specific conditions or with the help of specific solvents. The thermal stability and thermal stability will be improved. After treatment, the thermoplastic starch material can maintain a relatively stable physical state of the toy within a higher temperature range.
[0044] Polylactic acid (PLA) is a polymer compound. As part of the raw materials for manufacturing children's toys, the basis for material selection and the explanation of technical solutions require the basic knowledge of the molecular chain structure, aggregation structure, physical properties and chemical properties of polylactic acid (PLA).
[0045] The molecular chain of polylactic acid PLA is composed of lactic acid units connected by ester chains. Lactic acid molecules are obtained from renewable resources (such as corn, wheat, etc.) through microbial fermentation or chemical synthesis of glucose. Corn, wheat and other starches are polysaccharides composed of glucose molecules as basic structural units. Therefore, from the source point of view, the two have a certain connection. In terms of chemical element composition, both are mainly composed of three elements: carbon (C), hydrogen (H), and oxygen (O).
[0046] Due to the presence of ester bonds in the molecular chain of polylactic acid (PLA), the flexibility of the molecular chain is limited to a certain extent. The ester bonds are easily broken under hydrolysis, heat, acid and alkali conditions, which also determines the degradability of polylactic acid (PLA). However, it also affects its stability for making toys. Therefore, the stability of polylactic acid (PLA) must be improved through modification.
[0047] Chemical modification method, cross-linking reaction, use a suitable cross-linking agent to cross-link polylactic acid PLA, small molecule glycerol and other polyol substances containing multifunctional groups, heated under appropriate conditions, adding catalysts, can react with the functional group hydroxyl or carboxyl on the polylactic acid PLA molecular chain to form a cross-linked network structure. This cross-linking structure can limit the movement of the molecular chain, thereby improving the stability of polylactic acid PLA.
[0048] Copolymerization modification, introducing rigid structural units, selecting monomer aromatic esters with rigid structures to copolymerize with polylactic acid PLA, the introduction of aromatic structures can increase the rigidity of the molecular chain, restrict the movement or interaction of the molecular chain, thereby improving the stability of polylactic acid PLA. Copolymerization with monomers containing stable energy groups, epoxy monomers, epoxy groups can react with hydroxyl or carboxyl groups on the polylactic acid PLA molecular chain during the reaction process to form more stable chemical bonds or structures, thereby enhancing the stability of the molecular chain.
[0049] End-capping modification is to cap the end groups of the polylactic acid PLA molecular chain. Since the end carboxyl or carboxyl group of the polylactic acid PLA molecular chain has high reactivity and is prone to degradation, the end groups are capped with small molecular compounds (such as acyl chloride, acid anhydride, etc.) to reduce the reactivity of the end groups, thereby improving the stability of polylactic acid PLA.
[0050] Physical modification, adding stabilizers, hindered phenol antioxidants (such as antioxidant 1010, etc.) or phosphite antioxidants (such as antioxidant 168, etc.). During the processing and use of polylactic acid PLA, oxygen will trigger oxidative degradation reactions. Antioxidants can capture free radicals, inhibit the occurrence of oxidation reactions, and improve the stability of polylactic acid PLA.
[0051] Add light stabilizers, benzotriazole light stabilizers (such as UV-326, etc.). This type of light stabilizer can absorb the energy of ultraviolet rays and prevent ultraviolet rays from destroying the ester bonds in the molecular chain of polylactic acid PLA, thereby improving its stability.
[0052] Physical blending, blending with other stable polymers, and blending with polycarbonate (PC) can protect PLA to a certain extent, affect the behavior of PLA molecular chains through physical interaction, and improve the overall stability. It can also be blended with natural polymer cellulose and nanomaterials (such as nano titanium dioxide (TiO 2 ), nano-montmorillonite (MMT), etc., are blended to improve the stability of polylactic acid PLA.
[0053] Control the processing technology. During the processing of PLA, such as shearing, mixing, injection molding, etc., strictly control the processing temperature, pressure, time and other parameters. Lowering the processing temperature can reduce the thermal degradation of the molecular chain. Optimizing the pressure and time parameters can also help maintain the integrity of the molecular chain, thereby improving the stability of PLA.
[0054] The aggregate structure of polylactic acid (PLA) is a semi-crystalline polymer. Under certain conditions, the PLA molecular chains can be orderly arranged in crystalline regions, while the uncrystalline parts constitute non-crystalline regions. The degree of crystallinity is affected by many factors, such as the stereo configuration, molecular weight, and processing conditions of lactic acid. Polylactic acid (PLA) can form a variety of crystalline forms, such as spherulites and fibrous crystals. Spherulites are the most common crystal forms of PLA, and their size and morphology are affected by processing conditions and additives. Fibrous crystals are formed under specific processing conditions. The unique aggregate structure of polylactic acid (PLA) makes its heat resistance, strength and modulus, toughness and elongation at break insufficient in mechanical properties, which need to be improved. Phase separation. In some cases, polylactic acid (PLA) will experience phase separation. In the blending system, PLA and other polymers will separate due to compatibility issues, forming different phase regions. The degree and morphology of phase separation will affect the performance of the blend. By scientifically and effectively improving the mechanical properties of polylactic acid (PLA), it can meet the standards for making toy materials.
[0055] Improve the heat resistance of polylactic acid (PLA): Add nucleating agents, which can increase the starting point of crystallization, promote the crystallization of polylactic acid (PLA), and increase the crystallinity. The increase in crystallinity makes it more difficult for the material to deform at high temperatures, thereby improving heat resistance. Inorganic nucleating agents such as talcum powder can increase the crystallization rate and crystallinity of PLA, thereby improving heat resistance.
[0056] Thermal annealing is a post-processing method that keeps the finished product at the glass transition temperature for a certain period of time after it is formed. This helps to improve the crystallinity of PLA. When the crystallinity increases, the heat resistance will also increase accordingly.
[0057] Blending with heat-resistant polymers: blending polylactic acid PLA with other polymer materials that have high heat resistance (such as polycarbonate (PC), polyacid fiber, etc.).
[0058] Adding inorganic nanofillers. Some inorganic nanofillers (such as nano-silica, nano-alumina, etc.) can not only improve the crystallinity of polylactic acid PLA, but also hinder the movement of molecular chains to a certain extent, thereby improving the heat resistance of the material.
[0059] Enhance the strength and modulus of PLA: Improve the crystallinity. The increase of crystallinity usually improves the strength and modulus of PLA. In addition to the above-mentioned addition of nucleating agents and annealing methods, the strength and modulus can also be improved by optimizing the processing conditions (such as adjusting the processing temperature, cooling rate, etc.) to promote crystallization.
[0060] Enhance the orientation of molecular chains: By stretching and extruding, the PLA molecular chains are oriented in a specific direction, which can significantly improve the strength and modulus of the material in the direction of polymerization.
[0061] Chemical modification: Introducing a cross-linking structure between polylactic acid (PLA) molecular chains can limit the movement of the molecular chains and improve the strength and modulus of the material.
[0062] Grafting modification: Grafting other functional groups or polymer chains onto the polylactic acid (PLA) molecular chain to improve its compatibility with other materials or impart specific properties, thereby indirectly improving the mechanical properties.
[0063] Controlling crystal morphology: By controlling crystallization conditions, such as temperature, cooling rate, etc., crystalline structures such as spherulites of different sizes and shapes can be obtained. Crystal structures of appropriate size and shape help to improve strength and modulus.
[0064] Adding reinforcement materials: Fiber reinforcement, compounding fiber materials (such as bamboo fiber, hemp fiber, carbon fiber, glass fiber, etc.) with polylactic acid PLA can significantly improve the strength and modulus of PLA. Fiber plays a reinforcing role in the matrix and bears most of the load.
[0065] Nanofiller reinforcement: Adding inorganic nanofillers (such as nano-silica, nano-alumina, carbon nanotubes, etc.) can form a good interface bonding with the polylactic acid PLA matrix. At the same time, nanofillers may also affect the crystallization behavior of PLA, thereby improving strength and modulus.
[0066] Constructing a special crystal form: forming stereocomposite crystals (SC crystal form). When left-handed polylactic acid (PLLA) and right-handed polylactic acid (PDLA) are blended in a certain proportion, stereocomposite crystals can be formed, which have a higher melting point, higher strength and modulus than pure polylactic acid PLA. The stereocomposite of polylactic acid (PLLA) and polylactic acid (PDLA) is prepared by solution blending method and used as a nucleating agent with good nucleating effect. When left-handed polylactic acid (PLLA) and right-handed polylactic acid (PDLA) coexist, a polylactic acid stereocomposite is formed. This complex can act as a nucleating agent during polymer crystallization, which can significantly accelerate the crystallization speed of the composite material and improve the crystallinity of the product. For thermoplastic starch composite materials, good crystallization performance helps to improve the mechanical properties and heat resistance of the material, making the toys more durable.
[0067] Improve the toughness of PLA: Rubber / elastomer toughening, blending rubber or elastomer with PLA is a common method to achieve toughening. Rubber or elastomer forms dispersed groups in the PLA matrix, which can absorb energy and hinder the expansion of cracks when subjected to external forces, thereby improving toughness (such as polybutadiene rubber, thermoplastic polyurethane elastomer (TPU), etc. blended with PLA).
[0068] Constructing a special microstructure: preparing a polylactic acid-PLA composite material with a core-shell structure, in which the core layer is a material with good toughness and the shell layer is PLA. This structure can improve toughness while maintaining the basic properties of PLA. Or preparing a polylactic acid-PLA blend with an interpenetrating grid structure can also help improve toughness.
[0069] Improve the elongation at break of polylactic acid PLA: Plasticizer modification, adding an appropriate amount of plasticizer can reduce the glass transition temperature of polylactic acid PLA, increase the mobility of the molecular chain, make the material more easily deformed when subjected to force, and thus improve the elongation at break. However, the addition of plasticizers may have a certain impact on properties such as strength and modulus, which requires a comprehensive balance.
[0070] Adjusting the crystal morphology: Controlling the crystallization conditions and obtaining a crystal structure of appropriate size and morphology will help improve the elongation at break. By adjusting the cooling rate and other methods, polylactic acid (PLA) can form more small-sized crystals, which can deform to a certain extent when subjected to force, thereby improving the elongation at break of the material.
[0071] The density of polylactic acid (PLA) is relatively high: the density is generally 1.2-1.3kg / L. Compared with some general plastics (such as polyethylene with a density of about 0.92-0.96kg / L), the density of polylactic acid (PLA) is relatively high, which means that at the same volume, the weight of PLA products is heavier. In terms of improving density, blending modification can reduce density. A polymer with a lower density than polylactic acid (PLA) and good compatibility with it, polycarbonate lactone (PPC), is selected. The polycarbonate lactone is pretreated and dried to remove moisture. The two are blended in a certain proportion and extruded at high temperature to obtain a polylactic acid (PLA)-PPC blend to reduce the density.
[0072] The melting point of polylactic acid (PLA) is relatively low, ranging from 155-185°C. Compared with some engineering plastics (polycarbonate has a melting point of about 220-230°C), the melting point is relatively low. In high temperature environments or applications that need to withstand high temperatures, polylactic acid (PLA) is prone to softening and deformation, limiting its scope of use in high temperature environments. Its melting point has high requirements on processing technology, and the temperature needs to be strictly controlled during processing. Excessive temperature can easily lead to thermal decomposition, degradation and other problems, affecting material properties and product quality.
[0073] Improvement of melting point: copolymerization modification improves the melting point, selects comonomers, and cyclic monomers such as caprolactone with a higher melting point are copolymerized with polylactic acid PLA, and polylactic acid PLA and caprolactone are purified separately to remove impurities and moisture. Using the ring-opening polymerization method, PLA and caprolactone are added to the reaction vessel in a certain molar ratio under the action of a suitable catalyst (such as stannous octoate, etc.). The reaction temperature is controlled at 120℃-180℃, and the reaction time is usually between several hours and tens of hours, which is determined according to the reaction process. At the same time, nitrogen and other inert gases are continuously introduced during the reaction to prevent oxidation. After post-treatment, the product is cooled, precipitated, filtered, washed, etc. after the reaction is completed to remove impurities such as unreacted monomers and catalysts to obtain polylactic acid PLA-caprolactone copolymer.
[0074] Nucleating agent modification improves the melting point. Nucleating agent selection is suitable for polylactic acid PLA nucleating agent, such as talcum powder, boron nitride, etc. PLA and nucleating agent are mixed in a high-speed mixer in a certain proportion, and modified polylactic acid (DLA) is obtained through high temperature, mixing and extrusion. During the processing, the nucleating agent promotes the crystallization of polylactic acid PLA and improves the crystallinity and melting point.
[0075] The glass transition temperature of polylactic acid (PLA) is relatively high, between 60-65°C. When the ambient temperature is close to or lower than the glass transition temperature, the molecular chain movement of the polylactic acid (PLA) material is restricted, the material becomes brittle, and the toughness and impact resistance decrease. This limits the application of polylactic acid (PLA) in low temperature environments and improves the glass transition temperature.
[0076] Plasticization modification reduces the glass transition temperature. Plasticizers are selected. Common plasticizers include tributyl citrate (TBC), glycerol, etc. The water content of PLA is removed, and the plasticizer is dried to remove water and impurities. The two are added into a high-speed mixer in a certain proportion for mixing. The modified PLA is obtained by high-temperature mixing and extrusion. During the processing, the plasticizer molecules are inserted between the PLA molecular chains, reducing the force between the molecular chains, thereby reducing the glass transition temperature.
[0077] Cross-linking modification increases the glass transition temperature. The cross-linking agent is selected, such as diisopropyl peroxide (DCP), and the PLA is dried in a drying oven to ensure that the moisture content is less than 0.5%. The two are added in a certain proportion and mixed evenly. The modified PLA is obtained by high-temperature mixing and extrusion. After post-treatment, the modified PCA is heated in an oven at a temperature of 120-160°C for a certain period of time. The specific time is determined according to the cross-linking agent and process requirements, so that the cross-linking agent triggers a cross-linking reaction between the molecular chains of the PLA to form a three-dimensional network structure, thereby increasing the glass transition temperature.
[0078] Polylactic acid PLA has a relatively high refractive index in optical performance. Compared with some common transparent plastics such as polyethylene (PE) and polypropylene (PP), polylactic acid PLA has a higher refractive index, which will affect the performance of the optical system in some optical applications. Polylactic acid PLA has limited stability to ultraviolet rays. When exposed to ultraviolet rays for a long time, the PLA molecular chain is prone to degradation and aging, resulting in decreased mechanical properties, reduced transparency, and yellowing. In terms of improving optical properties and reducing refractive index, it is necessary to improve optical properties and reduce refractive index.
[0079] Blending modification, select polymers with low refractive index and good compatibility with polyacid (PLA), fluorinated polymers, dry polylactic acid PLA and fluorinated polymers in a vacuum drying oven to remove moisture. Through high-temperature mixing and extrusion, modified polylactic acid PLA with low refractive index is obtained.
[0080] For surface coating treatment, select inorganic or organic coating materials with low refractive index, silica solution or specific silicone coating materials. Clean the surface of the PLA product to remove oil and impurities, wipe the surface of the product with solvent materials, or use plasma treatment to reduce the refractive index of the product.
[0081] In addition, in order to improve the UV stability, a UV absorber is added, and benzotriazole UV absorber is selected. Polylactic acid PLA and the UV absorber are mixed in a certain proportion, and then extruded at high temperature to obtain modified polylactic acid PLA with improved UV stability.
[0082] In terms of air permeability, the gas barrier property of polylactic acid PLA needs to be improved. The polylactic acid PLA film has certain air permeability, but for some packaging applications with high gas barrier requirements, such as food preservation packaging, its ability to block oxygen, water vapor and other gases is relatively insufficient. To improve the air permeability, choose ethylene-vinyl alcohol copolymer (EVOH), a material with good gas barrier properties. Polylactic acid PLA and ethylene-vinyl alcohol are dried separately, and a multilayer composite structure is prepared by high-temperature mixing co-extrusion or lamination process to obtain an ideal gas barrier performance material.
[0083] PLA has poor weather resistance and outdoor durability. In outdoor environments, PLA is easily affected by sunlight, temperature, humidity and other factors, causing degradation and aging. After long-term outdoor exposure, its mechanical and chemical properties will gradually decline, and the molecular chain movement of PLA will be restricted, making it more brittle and prone to breakage.
[0084] Improve weather resistance, add antioxidants and light stabilizers, select antioxidants such as hindered phenol antioxidants, light stabilizers such as hindered amine light stabilizers. Through blending, high-temperature mixing and extrusion, modified polylactic acid PLA is obtained.
[0085] Plasma surface treatment removes dust, oil and other impurities from the surface of polylactic acid (PCA) products. The products are placed in plasma treatment equipment and treated with oxygen or nitrogen plasma. Plasma treatment can introduce active groups on the surface of the products and improve the stability of the surface.
[0086] By explaining the basic knowledge of the molecular chain structure, aggregation structure, physical properties and chemical properties of plant starch and polylactic acid PLA, as well as the knowledge of performance improvement methods and processing knowledge, it is shown that the selection of these two natural, safe, environmentally friendly and biodegradable raw materials for manufacturing children's toys provides a scientific basis and explains the rationality of material selection. At the same time, these basic knowledge provides a basis for determining the process parameters.
[0087] After studying the relevant knowledge and experiments on plant starch, we analyzed from a scientific perspective, prepared a thermoplastic starch material and improved its physical properties. We used corn starch grafting modification as a compatibilizer, and started the modification and grafting from the reducing end of the corn starch molecular chain to better improve the compatibility of plant starch.
[0088] The homemade corn starch compatibilizer in the present invention is achieved by the following technical scheme: A corn starch compatibilizer is prepared by modifying and grafting the reducing end of the end group of the corn starch molecular chain: Corn starch is a polysaccharide composed of glucose molecules, and its molecular chain has certain regularity and crystallinity. However, this structure also leads to some shortcomings in the physical properties of thermoplastic corn starch, such as greater brittleness and poor water resistance.
[0089] Introducing flexible chain segments: Containing functional groups such as hydroxyl and ester groups, after being grafted onto the corn starch molecular chain, flexible chain segments can be introduced to increase the flexibility and deformability of the molecular chain, thereby improving the toughness and impact resistance of thermoplastic corn starch.
[0090] Improve water resistance: Hydroxyl groups can form hydrogen bonds with water molecules, increasing the hydrophilicity of the material. But at the same time, the presence of ester groups can increase the hydrophobicity of the material. By adjusting the amount of grafting, the hydrophilicity and hydrophobicity of the material can be balanced to a certain extent, improving the water resistance of thermoplastic corn starch.
[0091] Improve compatibility: Contains functional groups such as carboxyl, which can form hydrogen bonds or ionic bonds after being grafted onto the molecular chain of corn starch, thereby improving the compatibility between the two monomers and corn starch, and improving the grafting efficiency and the performance stability of the material.
[0092] Enhanced cross-linking: Carboxyl groups can undergo esterification or cross-linking reactions with hydroxyl groups or other functional groups on the corn starch molecular chain to form a three-dimensional network structure, increasing the strength and heat resistance of the material.
[0093] The scientific principle of the monomer hydroxyethyl methacrylate being grafted onto the reducing end of the terminal group of the corn starch molecular chain: Free radical initiation: free radicals are generated under the action of the initiator potassium persulfate. Potassium persulfate decomposes under heat to produce sulfate radicals, which can attack the active hydrogen at the reducing end of the terminal group of the corn starch molecular chain, causing the starch molecular chain to produce free radical sites.
[0094] Double bond addition reaction: Hydroxyethyl methacrylate molecules contain a carbon-carbon double bond (C = C), which has a high reactivity. The free radicals at the end of the starch molecular chain can react with the double bond of the hydroxyethyl methacrylate molecule, thereby grafting hydroxyethyl methacrylate onto the corn starch molecular chain. At the same time, the hydroxyethyl ester group (-OCH 2 CH 2 The hydroxyl groups (-OH) in starch molecules can form hydrogen bonds or other interactions to further stabilize the grafted structure.
[0095] The scientific principle of the monomer itaconic acid grafted to the reducing end of the terminal group of the corn starch molecular chain: Reaction of carboxyl group and reducing end: Itaconic acid molecule contains two carboxyl groups (-COOH) and one carbon-carbon double bond. During the reaction, the carboxyl group of itaconic acid can undergo esterification reaction or other forms of chemical reaction with the aldehyde group or hemiacetal group at the reducing end of the terminal chain of corn starch molecule to form a chemical bond.
[0096] Grafting reaction involving double bonds: The carbon-carbon double bonds of itaconic acid can also react with free radicals generated by starch molecular chains under the initiation of free radicals to achieve grafting. In addition, the carboxyl group of itaconic acid can also hydrogen bond or interact with the hydroxyl group in the starch molecule to enhance the grafting effect.
[0097] Synergistic grafting effect of hydroxyethyl methacrylate and itaconic acid: hydroxyethyl methacrylate and itaconic acid have a synergistic effect in the grafting process. The reaction of the carboxyl group of itaconic acid with the reducing end of the terminal group of the corn starch molecular chain can provide more active sites for the subsequent grafting of hydroxyethyl methacrylate, or change the chemical environment of the terminal group of the starch molecular chain, making it more conducive to the grafting of hydroxyethyl methacrylate. At the same time, the grafting of hydroxyethyl methacrylate may also affect the reaction mode and degree of itaconic acid and starch molecules. The two cooperate with each other to improve the overall grafting efficiency and grafting effect.
[0098] Correlation between the prepared compatibilizer and the compatible structural similarity and interaction between plant starch and polylactic acid PLA: The role of hydroxyethyl methacrylate: Since the grafted corn starch molecules contain the structural unit of hydroxyethyl methacrylate, its hydroxyethyl ester group can form hydrogen bonds with the ester group (-COO-) in the polylactic acid PLA molecule. Polylactic acid is a polyester polymer. The ester group in the molecule has a certain polarity and can form hydrogen bonds with the oxygen and hydrogen atoms of the hydroxyethyl ester group, thereby enhancing the compatibility between corn starch and polylactic acid PLA.
[0099] The role of itaconic acid: After itaconic acid is grafted onto the corn starch molecule, its carboxyl group (-COOH) can produce an acid-base interaction with the ester group in the polylactic acid (PLA) molecule. This acid-base interaction can form a special mutual attraction between corn starch and polylactic acid, which helps the two to mix and be compatible better at the microscopic level.
[0100] Improved interfacial compatibility: In composite materials composed of plant starch and polylactic acid (PLA), the interfacial compatibility between the two is a key factor affecting the material performance. By synergistically grafting hydroxyethyl methacrylate and itaconic acid to the reducing end of the end group of the corn starch molecular chain, the surface properties and chemical structure of corn starch are changed, and the interaction between it and polylactic acid is enhanced. At the interface, the grafted corn starch molecules can better combine with the polylactic acid (PLA) molecules, reduce phase separation, and improve the mechanical properties, thermal properties and other comprehensive properties of the material.
[0101] Increase the entanglement between molecules: The flexibility and spatial conformation of the grafted corn starch molecular chain may change due to the introduction of the structural units of hydroxyethyl methacrylate and itaconic acid. These changed corn starch molecular chains can be more entangled with the polylactic acid molecular chains, just like intertwined ropes, further strengthening the connection between the two, thereby improving the compatibility of plant starch and polylactic acid.
[0102] There is an invention patent with publication number CN115197404A, which grafts caprolactone onto plant starch as a compatibilizer for starch-modified and degradable materials.
[0103] The present invention adopts the reducing end of the terminal group of corn starch molecular chain for modification and grafting, and prepares a corn starch compatibilizer through the following process: 1. Raw material formula (by weight percentage): 10kg corn starch (select high-purity, low-impurity corn starch with a water content controlled at 10% - 15% as the basic material); Ascorbic acid vitamin C (reducing agent) 0.5kg; used as a reducing agent to pre-treat the reducing end of the terminal group of the corn starch molecular chain. It can reduce the oxidized functional groups existing in the terminal group of the starch molecular chain, increase the active sites available for grafting reaction, and create favorable conditions for the subsequent grafting reaction of the monomer.
[0104] 3kg of hydroxyethyl methacrylate (monomer); used as a monomer for grafting reaction with corn starch. Since the grafted starch molecules contain the structural unit of hydroxyethyl methacrylate, they can form hydrogen bonds with the ester groups in the polylactic acid (PLA) molecules through the hydroxyethyl ester groups, thereby improving the compatibility of starch and polylactic acid and improving the performance of the composite material.
[0105] Itaconic acid (monomer) 1.5 kg; used as a monomer for grafting reaction with corn starch. The carboxyl group of itaconic acid can undergo chemical reactions such as esterification reaction with the aldehyde group or hemiacetal group at the reducing end of the terminal group of the corn starch molecular chain, and its carbon-carbon double bond can participate in the grafting reaction initiated by free radicals. The carboxyl group in the grafted itaconic acid structural unit can produce acid-base interaction with the ester group in the polylactic acid PLA molecule, thereby improving the compatibility of starch and polylactic acid PLA.
[0106] Potassium persulfate (initiator) 0.2 kg; used as an initiator in the reaction. Potassium persulfate decomposes under heat to produce sulfate radicals, which can attack the active hydrogen at the reducing end of the terminal group of the corn starch molecular chain, causing the starch molecular chain to produce free radical sites, thereby initiating the grafting of monomers (hydroxyethyl methacrylate and itaconic acid) with starch.
[0107] 2. Process steps 1. Reduction pretreatment of corn starch Solution preparation: In a clean bucket, accurately weigh 0.5 kg of ascorbic acid vitamin C and add 20 L of distilled water. Use a stirring rod to stir manually to completely dissolve the ascorbic acid vitamin C in the distilled water to obtain an ascorbic acid vitamin C solution; Reduction reaction, slowly add 10kg corn starch to the prepared ascorbic acid vitamin C solution, stirring while adding to prevent the corn starch from agglomerating; The mixed system was transferred to a 50 L reactor, and the stirrer was turned on under nitrogen protection, and the stirring speed was set to 200-300 rpm; the reactor was heated to raise the system temperature to 55° C., and the reaction was continued at this temperature under nitrogen protection for 2 hours.
[0108] (II) Grafting reaction Preparation of monomer mixture: In a clean container, accurately weigh 3 kg of hydroxyethyl methacrylate and 1.5 kg of itaconic acid, and stir them evenly with a stirring rod to obtain a monomer mixture; Preparation of initiator solution: weigh 0.2 kg of potassium persulfate, add 5 L of distilled water, and stir with a stirring rod until the potassium persulfate is completely dissolved to prepare a potassium persulfate solution; Graft copolymerization reaction, reducing the pretreated corn starch reaction system in a reactor, maintaining the temperature at 55-60°C under nitrogen; Use a peristaltic pump to slowly drop the monomer mixture into the reactor, the drop speed is controlled at 100-150mL / min, the stirring speed is maintained at 300-400rpm during the drop addition, and the drop addition time is about 30-45 minutes. After the drop addition is completed, continue stirring for 10 minutes to disperse the monomer evenly in the reaction system. The whole process is carried out under nitrogen protection; then, use another peristaltic pump to slowly drop the potassium persulfate solution into the reactor, the drop speed is also controlled at 300-400mL / min, and the drop addition time is 15-20 minutes. The whole process is carried out under nitrogen protection.
[0109] After the initiator is added dropwise, the temperature of the reactor is maintained at 60-80°C, and the reaction is stirred for 4-6 hours to allow the grafting reaction to proceed fully. The stirring speed is maintained at 300-400rpm during the reaction. The entire process is carried out under nitrogen protection.
[0110] (III) Post-processing Product separation: After the grafting reaction is completed, the reaction product in the reactor is transferred to a centrifuge and centrifuged at 3000-5000rpm for 5-10 minutes to separate the solid (grafted product) from the liquid (unreacted monomer, initiator, etc.), the upper clear liquid is discarded, and the solid product at the lower layer is collected; Washing: Add the collected solid product to 20L of deionized water and stir in a reactor for 30-40 minutes at a stirring speed of 200-300rpm. The purpose of this step is to wash away impurities such as residual monomers and initiators; Transfer the reaction product to the centrifuge again, centrifuge at 3000 - 5000 rpm for 5 - 10 minutes, pour out the upper water; repeat the washing step 2 -3 times to ensure that the impurities are washed away.
[0111] Drying, placing the washed solid product in a vacuum drying oven, setting the temperature to 50-60°C, the vacuum degree to -0.08 to -0.1MPa, and the drying time to 24-48 hours, until the product has a constant weight, to obtain the final corn starch compatibilizer, such as Figure 1 , which are the process steps for preparing corn starch compatibilizer.
[0112] The prepared corn starch compatibilizer is used in thermoplastic plant starch composites to improve the interfacial compatibility: 1. Chemical structure complementarity The hydroxyethyl methacrylate and itaconic acid grafted on corn starch create chemical structural complementarity between plant starch and polylactic acid PLA. Polylactic acid PLA is a linear polyester with rich ester groups in the molecular chain. In the grafted starch molecules, the hydroxyethyl ester group in hydroxyethyl methacrylate can form hydrogen bonds with the ester group of polylactic acid PLA, and the carboxyl group of itaconic acid and the ester group of polylactic acid produce acid-base interaction. This complementary interaction based on chemical structure is a key factor in improving compatibility, making the mixing of starch and polylactic acid PLA more uniform at the molecular level and reducing phase separation.
[0113] 2. Enhanced interface performance In plant starch-PLA composites, the properties of the interface have a huge impact on the overall performance of the material. The compatibilizer significantly improves the interfacial compatibility between the two. When no compatibilizer is added, due to the difference in the chemical structure of starch and PLA, the interfacial bonding force is weak, and cracks and delamination are easily generated at the interface when subjected to external force. After adding this compatibilizer, the grafted plant starch molecules can be tightly combined with the PLA molecules at the interface, like a "bridge", which enhances the adhesion of the interface, thereby improving the mechanical properties of the composite material, such as tensile strength, bending strength and impact toughness.
[0114] 3. Improved dispersion The presence of compatibilizer helps to improve the dispersibility of plant starch in the polylactic acid PLA matrix. The uniform dispersion of plant starch particles in polylactic acid PLA is an important aspect to achieve good compatibility. The interaction between the grafted plant starch molecules and polylactic acid PLA reduces the tendency of plant starch particles to agglomerate, allowing the plant starch to be more evenly dispersed in polylactic acid PLA, forming a more stable composite material system.
[0115] The prepared corn starch compatibilizer is used in thermoplastic plant starch composites to improve the thermoplasticity significantly: 1. Improved thermal stability In thermoplastic starch materials, thermal stability is a key performance indicator. The components in the compatibilizer have a positive effect on the thermal stability of the grafted starch. The grafting of itaconic acid may increase the degree of cross-linking between starch molecular chains and reduce the degradation and decomposition reactions of starch molecules when heated. At the same time, the presence of hydroxyethyl methacrylate changes the thermal motion characteristics of starch molecules, allowing the entire thermoplastic starch material to maintain good structural integrity at higher temperatures, broadening its application temperature range.
[0116] 2. Processing performance optimization For the processing of thermoplastic starch materials, the role of compatibilizers cannot be ignored in toy extrusion, injection molding and other molding processes. Because it improves the compatibility of starch and polylactic acid and the dispersibility of starch, the fluidity of the material during processing is better. During the extrusion process, the material can pass through the screw and mold more smoothly, reducing energy loss and equipment wear during the processing. In the injection molding process, it can also better fill the mold cavity and improve the quality and dimensional accuracy of the molded products.
[0117] After studying the relevant knowledge and experiments of polylactic acid, we analyzed from a scientific point of view, prepared a thermoplastic starch material and improved its physical properties. When using polylactic acid (PLA) grafted modified polylactic acid as a compatibilizer, we can start from the structure of polylactic acid (PLA) for modification and grafting to make it more compatible with plant starch.
[0118] The self-made polylactic acid PLA compatibilizer described in the present invention is achieved by the following technical solutions: A polylactic acid PLA compatibilizer is prepared by introducing a branched structure into the main chain of polylactic acid PLA: Principle: Introducing a branched structure on the main chain of PLA can change the spatial conformation and physical and chemical properties of PLA molecules. The branched structure can increase the flexibility of PLA molecules and their ability to interpenetrate and entangle with plant starch molecules; when the branched chain carries a functional group that can interact with plant starch, the branched structure can also destroy the regularity of the PLA molecular chain and reduce its crystallinity, making it easier to be compatible with plant starch, a material with a more amorphous structure; when the grafted PLA is mixed with plant starch, it can be better compatible with plant starch due to the interaction between the amino groups on the branched chain and the hydroxyl groups of starch and the influence of the branched structure on the crystallinity of PLA.
[0119] The monomer is preferably hydroxypropyl acrylate, which is grafted onto the main bond of polylactic acid (PLA) to introduce the scientific principle of the branched structure: Hydroxypropyl acrylate (HPA) molecules contain carbon-carbon double bonds (C=C) and hydroxyl groups (-OH). Under appropriate reaction conditions, the carbon-carbon double bonds can be opened and react with the active sites on the main bond of PLA, thereby grafting HPA onto the PLA molecular chain. After grafting, the hydroxyl and other functional groups of HPA become the branched parts of the PLA molecule. Through the free radical polymerization reaction initiated by the free radical initiator, the carbon-carbon double bonds of hydroxypropyl acrylate can be chemically bonded to the main bond of PLA to achieve grafting.
[0120] The scientific principle of introducing a branched structure by grafting ethyl lactate onto the main bond of polylactic acid (PLA) is that there are active groups such as ester groups (-COO-) in the ethyl lactate molecule, which can react chemically with the corresponding sites on the main bond of PLA, such as transesterification, thereby connecting ethyl lactate to the PLA molecular chain to form a branched structure. At a certain temperature, the ester group of ethyl lactate undergoes an ester exchange reaction with the ester bond in the PLA molecule, so that ethyl lactate is successfully grafted.
[0121] Synergistic grafting effect of hydroxypropyl acrylate and ethyl acrylate: 1. Mutual influence of reactivity: The active functional group hydroxyl of hydroxypropyl acrylate affects the reactivity of ethyl lactate during the grafting process. Hydroxypropyl acrylate first reacts with the active sites on the polylactic acid side chains, changing the local chemical environment, making it easier for ethyl lactate to approach and undergo grafting reaction.
[0122] 2. Steric hindrance synergy: During the grafting process, the molecular structures of the two monomers have a steric hindrance effect. When the two monomers are grafted together, they can adjust each other's spatial positions to avoid excessive spatial hindrance. The molecular shape and size of ethyl lactate complement those of hydroxypropyl acrylate, allowing them to be more reasonably distributed on the polylactic acid side chains, improving the grafting efficiency.
[0123] 3. Influence of chemical bonding: The two monomers may affect each other through chemical bonding. The double bond in hydroxypropyl acrylate interacts with the ester group in ethyl lactate during the grafting reaction. This interaction may promote the co-grafting of the two on the polylactic acid side chain to form a more stable grafted structure.
[0124] Compatibility correlation between the prepared compatibilizer and plant starch and polylactic acid (PLA): 1. Improve interfacial compatibility: The compatibility of plant starch with polylactic acid (PLA) is usually poor. By grafting branched structures such as hydroxypropyl acrylate and ethyl lactate on the main bond of polylactic acid (PLA), the polarity and flexibility of polylactic acid (PLA) molecules can be increased. These branched structures can form more interactions with plant starch molecules, such as hydrogen bonds, van der Waals forces, etc., thereby improving the interfacial compatibility between the two and enabling plant starch to be better dispersed in the polylactic acid (PLA) matrix.
[0125] 2. Adjust the performance matching degree: Plant starch and polylactic acid PLA have different performance characteristics. The polylactic acid PLA with grafted branched structure can adjust its performance to a certain extent, making it more compatible with the performance of plant starch. Increasing the flexibility and processability of polylactic acid (PLA) makes it easier to blend with plant starch to prepare composite materials with excellent performance.
[0126] 3. Provide reaction sites: The functional groups on the branched structure (such as hydroxyl groups, etc.) can provide more reaction sites for further chemical reactions or physical interactions between plant starch and polylactic acid PLA, which helps to enhance the bonding force between the two and improve the stability and performance of the composite material.
[0127] There is a patented polylactic acid compatibilizer with publication number 112661911A, which is used in plant fiber composite materials.
[0128] The polylactic acid PLA compatibilizer of the present invention is achieved by the following process: 1. Raw material formula (by weight percentage) Polylactic acid PLA: 100g (molecular weight 100000-500000, as the basic material of the main chain structure); Hydroxypropyl acrylate (monomer): 15g; the double bonds in hydroxypropyl acrylate can react with the main chain of polylactic acid to form side chains under the action of an initiator, and its hydroxypropyl group helps to improve compatibility with other substances; Ethyl lactate (monomer): 15g; similar to the structure of polylactic acid, it introduces side chains into the main chain through reactions such as ester exchange, while enhancing the overall compatibility; Potassium persulfate (initiator): 2g. The free radicals generated by the decomposition of potassium persulfate can initiate the reaction between the monomer and the main chain of polylactic acid. Ethyl acetate (solvent): 200 mL; it can effectively dissolve polylactic acid and allow the reaction to proceed in a homogeneous system.
[0129] Propylene glycol (auxiliary agent): 15g; as a solvent and auxiliary agent, it adjusts the polarity and reactivity of the reaction system, promotes the reaction and helps to improve compatibility.
[0130] Process steps 1. Raw material pretreatment 1. Dissolution of polylactic acid: Add 100g of polylactic acid into a three-necked flask containing 200mL of ethyl acetate and stir to dissolve at room temperature. Set the stirring speed to 200-300rpm until the polylactic acid is completely dissolved to form a transparent solution. This process may take 1-2 hours; 2. Mixing monomers and additives: In another container, mix 15g of hydroxypropyl acrylate, 15g of ethyl lactate and 15g of propylene glycol to form a mixed solution for later use; (II) Triggering reaction 1. Preparation of initiator solution: Dissolve 1.5 g potassium persulfate in 15 mL distilled water to prepare an initiator solution; 2. Grafting reaction: Heat the reaction vessel (containing ethyl acetate solution of polylactic acid) to 60-70°C, then slowly drop the mixture of monomer and additive into the three-necked flask of the reaction vessel, and control the dropping time to 30-40 minutes. During the dropping process, keep the stirring speed at 300-400rpm. The whole process is carried out under nitrogen protection; After the addition is completed, continue stirring for 10-15 minutes under nitrogen protection, and then slowly add the initiator solution dropwise to the three-necked flask in the reaction vessel for 10-15 minutes; After the initiator is added dropwise, the reaction is continued at 60-70°C for 3-5 hours to allow the monomer to fully react with the polylactic acid main chain and introduce a branched structure into the polylactic acid, all the time under nitrogen protection.
[0131] (III) Post-processing 1. Solvent removal: After the reaction is completed, the reaction mixture is transferred to a rotary evaporator and the ethyl acetate solvent is removed by reduced pressure distillation at 40-50°C to obtain a grafted product; 2. Product purification: Wash the grafted product with an appropriate amount of ethanol 2-3 times to remove unreacted monomers and additives, and then dry it in a vacuum drying oven at 40-50°C for 24-48 hours until the product has a constant weight to obtain the final polylactic acid compatibilizer; Figure 2 , which are the process steps for preparing polylactic acid (PLA) compatibilizer; The prepared polylactic acid PLA compatibilizer is used in thermoplastic plant starch composites to improve the significance of the interface: 1. Chemical structure interactions Interaction between hydroxyl and ester groups: Plant starch contains a large number of hydroxyl groups (-OH). In the prepared polylactic acid PLA compatibilizer, the hydroxypropyl group (-OCH 2 CH(OH)CH 3 ) can form hydrogen bonds with the hydroxyl groups of plant starch. At the same time, the ester group (-COO-) in the molecular chain of polylactic acid PLA itself also interacts with the hydroxyl groups of starch. This multiple hydrogen bond and polar interaction makes the combination of polylactic acid and plant starch at the interface tighter, reducing the phase separation phenomenon.
[0132] Affinity of similar structures: Ethyl lactate monomer has a similar structure to polylactic acid (PLA), which makes the compatibilizer have good affinity with polylactic acid. When compounded with plant starch, the compatibilizer can act as a "bridge" between polylactic acid and plant starch, shortening the molecular distance between the two, promoting the interaction between the two, and improving the interfacial compatibility.
[0133] 2. Reduce surface energy differences The surface energy difference between PLA and plant starch is large, which is one of the important factors that lead to their incompatibility in composite materials. The addition of compatibilizer can reduce this surface energy difference. Different functional groups in the compatibilizer molecules (such as hydroxypropyl, ester group, etc.) can adjust the molecular arrangement of PLA and plant starch at the interface, making the surface energy of the two closer, thereby improving the wettability and adhesion between the two and improving the interfacial compatibility.
[0134] The prepared polylactic acid PLA compatibilizer is used in thermoplastic plant starch composites to improve the dispersibility: 1. Steric hindrance effect The compatibilizer forms a "wrapping layer" between polylactic acid (PLA) and plant starch. Since the compatibilizer molecules have a certain branched structure, these branches produce a steric hindrance effect around the polylactic acid (PLA) and plant starch particles, preventing the agglomeration of plant starch particles. When the plant starch particles are dispersed in the polylactic acid matrix, the branched structure of the compatibilizer molecules prevents the starch particles from approaching each other and agglomerating together, thereby improving the dispersibility of the plant starch in polylactic acid (PLA).
[0135] 2. Reduce interfacial tension Compatibilizers reduce the interfacial tension between polylactic acid (PLA) and plant starch. In the preparation of composite materials, lower interfacial tension helps to evenly disperse plant starch particles in the polylactic acid matrix. Just like adding emulsifiers to an oil-water system to reduce the interfacial tension between oil and water, compatibilizers make it easier for plant starch to be dispersed in the polylactic acid (PLA) matrix, forming a more uniform composite material structure.
[0136] The prepared polylactic acid PLA compatibilizer is used in thermoplastic plant starch composites to enhance the mechanical properties: 1. Stress transfer In thermoplastic plant starch composites, good interfacial compatibility and uniform dispersion of plant starch contribute to the transfer of stress in the material. When the material is subjected to external force, the stress can be effectively transferred from the PLA matrix to the plant starch phase through the good interface between PLA-compatibilizer-plant starch, so that the entire composite material can jointly withstand the external force, thereby improving the tensile strength, bending strength and other mechanical properties of the material.
[0137] 2. Toughening effect The presence of compatibilizers can change the fracture behavior of materials. By improving interfacial compatibility and increasing dispersibility, compatibilizers can play a buffering and energy-consuming role between polylactic acid (PLA) and plant starch when the material is impacted. During the crack propagation process, the interaction between compatibilizer molecules and between polylactic acid (PLA) and plant starch will consume energy, preventing further crack propagation, thereby improving the toughness of the material.
[0138] The prepared polylactic acid PLA compatibilizer is used in thermoplastic plant starch composites to improve the processing performance: 1. Improved liquidity During the thermoplastic processing of toys, the compatibilizer can improve the fluidity of the composite material. Since it improves the compatibility and dispersibility between polylactic acid PLA and plant starch, the internal friction of the composite material during processing is reduced. In the extruder, the material can pass through the screw and mold more smoothly, reducing energy loss and equipment wear during processing, and is also conducive to obtaining molded products with higher dimensional accuracy.
[0139] 2. Improved thermal stability The compatibilizer, which has a similar structure to polylactic acid, has a positive effect on the thermal stability of the composite material. During processing, especially at higher temperatures, the compatibilizer can reduce the thermal degradation of plant starch and polylactic acid (PLA). During the toy injection molding process, at higher processing temperatures, the compatibilizer can stabilize the molecular structure and prevent premature decomposition by interacting with polylactic acid (PLA) and plant starch molecules, thereby improving the processing stability of the material.
[0140] The present invention aims to manufacture children's toys from plant starch, which is achieved through the following processes and steps: The overall manufacturing process steps of children's toys made from plant starch: 1. Raw material preparation Corn starch raw material: Select high-purity corn starch, the purity of which should be no less than 95%. Pre-treat the selected corn starch. First, place the corn starch in an airflow dryer and dry it for 2-5 hours at a temperature of 50-60℃ and an airflow velocity of 1.5-2.5m / s to reduce the moisture content of the corn starch to 0.5%-1%. Then, place the dried corn starch in a planetary ball mill and mill it at a speed of 300-500r / min for 0.5-2 hours. The corn starch after ball milling meets the 80-200 mesh standard after vibrating screen.
[0141] Polylactic acid raw material: Select polylactic acid (PLA) with a suitable molecular weight (100,000 - 500,000). Before use, the polylactic acid is crushed into 1-2 mm small particles by a double-roll crusher, placed in a vacuum drying oven, and dried for 3 - 5 hours at a temperature of 60 - 80 ° C and a vacuum degree of - 0.08 to - 0.1 MPa to remove moisture and small molecular impurities.
[0142] 2. Mixing process The pretreated corn starch and polylactic acid PLA, as well as corn starch compatibilizer, polylactic acid compatibilizer, nucleating agent, antioxidant, antistatic agent, and colorant are mixed in a high-speed mixer according to weight percentage. The stirring paddle speed of the high-speed mixer is set to 800-1200r / min, and the mixing time is 10-30 minutes. During the mixing process, nitrogen is introduced into the mixer at a nitrogen flow rate of 5-10L / min to prevent the material from being oxidized during the mixing process.
[0143] After mixing, the obtained premix is put into a twin-screw extruder for blending and extrusion. The screw length-diameter ratio of the twin-screw extruder is 30:1 - 52:1, and the screw speed is 100 - 200r / min. Temperature settings of each section of the extruder: 1. Feeding section, this section needs to have a large conveying capacity to ensure that the material can enter the screw stably and continuously, and the temperature range is set at 100℃-130℃. 2. Solid conveying section, compact the loose powdered material and fill it in the screw groove to prepare for the melting and plasticization of the material downstream. The temperature range is 120℃-140℃. Set the exhaust port to reduce the gas content in the material. 3. Melting section, this section is the key stage for the material to transform from solid to liquid. Sufficient heat and shear force need to be provided to allow the plant starch and polylactic acid to completely melt and mix evenly. The temperature range is set at 150℃-180℃. 4. Mixing section. In this stage, the plant starch and polylactic acid are fully mixed to form a uniform melt, and the dispersed phase size of the material is further reduced to improve the mixing effect. The temperature range is 155℃-170℃. 5. Exhaust section. It is mainly used to discharge moisture, entrained air and volatile components in the material so that the gas can be discharged smoothly. The temperature range is 140℃-160℃. 6. Homogenization section: Make the material at the die mouth have a certain density, and further mix it to finally achieve the purpose of smooth extrusion molding. The temperature range is 150℃-165℃. This temperature gradient setting ensures that the plant starch and polylactic acid PLA are fully blended and appropriate physical and chemical reactions occur to form a uniform composite material. Extrusion, cooling, and hot air drying obtain a plant starch composite material; such as Figure 3 , designed for 6-stage temperature gradient of extruder.
[0144] 3. Molding process Injection molding: The composite material is sent to the injection molding machine for injection molding. The injection pressure of the injection molding machine is 8-12MPa, the injection temperature is 170-190℃, and the holding time is 5-10 seconds. According to the design requirements of different children's toys, the corresponding mold is used for injection molding. The cooling system of the mold adopts circulating water cooling, and the water temperature is 10-20℃ to ensure that the toy has good shape and dimensional accuracy when demolding; The extruded composite material can be directly transported to the barrel of the injection molding machine through a constant temperature pipeline for injection molding, which can reduce the energy consumption of the melting process of the injection molding machine and also reduce the changes in material properties that may be caused by the secondary melting of the granular material; Blow molding: The composite material is sent to the blow molding machine for blow molding. The blow molding temperature is 170-190℃, and the clamping force should be large enough to ensure that the mold will not leak during the blowing process. The blowing pressure is between 0.2MPa-0.6MPa, and the blowing time is between a few seconds and tens of seconds.
[0145] The cooling method adopts air cooling, and the fan blows air to the toy to cool it quickly. The extruded composite material can be directly transported to the barrel of the blow molding machine through a constant temperature pipeline for blow molding, which can reduce the energy consumption of the blow molding machine melting link and reduce the material performance changes that may be caused by the secondary melting of the granular material.
[0146] 4. Post-processing process Annealing treatment: The formed children's toys are placed in an annealing furnace for annealing treatment. The annealing temperature is 80-100℃ and the annealing time is 2-4 hours. The annealing treatment eliminates the residual stress inside the toy and improves the physical properties of the toy.
[0147] Painting treatment: Toy surface painting, air spraying, the paint is atomized into tiny particles by compressed air, and then sprayed onto the surface of the toy. According to the requirements, the toys are decorated with printing and other decorations to increase their beauty and attractiveness.
[0148] Surface treatment: Use non-toxic, biodegradable natural plant wax rice bran wax to treat the surface of the toy. Soak the toy in a 5% to 10% plant wax solution at a temperature of 60-80℃ for 1-3 minutes, then take it out and dry it. The plant wax forms a protective film on the surface of the toy, which improves the wear resistance and stain resistance of the toy. At the same time, the plant wax itself has certain antibacterial properties, which further ensures the safety of children's use. Figure 4 , which is a process step for thermoplastic toy manufacturing.
[0149] Example 1: Preparation of corn starch compatibilizer: The present invention adopts the reducing end of the terminal group of corn starch molecular chain for modification and grafting, and prepares a corn starch compatibilizer through the following process: 1. Raw material formula (by weight percentage) 1. 200kg corn starch (choose high-purity, low-impurity corn starch with a water content of 10% - 15% as the basic material) 2. Ascorbic acid vitamin C (reducing agent): 10kg As a reducing agent, it pre-treats the reducing end of the terminal group of the corn starch molecular chain. It can reduce the oxidized functional groups existing in the terminal group of the starch molecular chain, increase the active sites available for grafting reaction, and create favorable conditions for the subsequent grafting reaction of monomers.
[0150] 3. Hydroxyethyl methacrylate (monomer): 60kg As a monomer, it is grafted with corn starch. Since the grafted starch molecules contain the structural unit of hydroxyethyl methacrylate, they can form hydrogen bonds with the ester groups in the polylactic acid (PLA) molecules through the hydroxyethyl ester groups, thereby improving the compatibility of starch and polylactic acid and improving the performance of the composite material.
[0151] 4. Itaconic acid (monomer): 30kg It is used as a monomer to undergo a grafting reaction with corn starch. The carboxyl group of itaconic acid can undergo chemical reactions such as esterification with the aldehyde group or hemiacetal group at the reducing end of the corn starch molecular chain, and its carbon-carbon double bond can participate in the grafting reaction initiated by free radicals. The carboxyl group in the grafted itaconic acid structural unit can produce an acid-base interaction with the ester group in the polylactic acid PLA molecule, thereby improving the compatibility of starch and polylactic acid PLA.
[0152] 5. Potassium persulfate (initiator): 4kg It is used as an initiator in the reaction. Potassium persulfate decomposes under heat to produce sulfate radicals, which can attack the active hydrogen at the reducing end of the terminal group of the corn starch molecular chain, causing the starch molecular chain to produce free radical sites, thereby initiating the grafting of monomers (hydroxyethyl methacrylate and itaconic acid) with starch.
[0153] 2. Process steps 1. Reduction pretreatment of corn starch 1. Solution Preparation In a clean large container, accurately weigh 10 kg of ascorbic acid vitamin C, add 400 L of distilled water, and stir to completely dissolve the ascorbic acid vitamin C in the distilled water to obtain an ascorbic acid vitamin C solution.
[0154] 2. Reduction reaction Slowly add 200 kg corn starch into the prepared ascorbic acid vitamin C solution, stirring while adding to prevent the corn starch from agglomerating.
[0155] The mixed system was transferred to a 1000 L multifunctional reactor equipped with a condenser and a nitrogen protection device, and the agitator was turned on under nitrogen protection, and the stirring speed was set to 200 - 300 rpm.
[0156] The reactor was heated to raise the system temperature to 55°C, and the reaction was continued with stirring at this temperature for 2 hours under nitrogen protection.
[0157] (II) Grafting reaction 1. Preparation of Monomer Mixture In a clean container, accurately weigh 60 kg of hydroxyethyl methacrylate and 30 kg of itaconic acid, and stir them evenly with a stirring rod to obtain a monomer mixture.
[0158] 2. Preparation of initiator solution In a clean container, weigh 4 kg of potassium persulfate, add 100 L of distilled water, and stir with a stirring rod until the potassium persulfate is completely dissolved to prepare a potassium persulfate solution.
[0159] 3. Graft copolymerization The corn starch reaction system after reduction pretreatment is maintained at 55-60° C. in a reactor under nitrogen.
[0160] Use a peristaltic pump to slowly drop the monomer mixture into the reactor, the drop speed is controlled at 2-5L / min, the stirring speed is maintained at 300-400rpm during the drop addition, and the drop addition time is about 30-45 minutes. After the drop addition is completed, continue stirring for 10 minutes to make the monomer dispersed evenly in the reaction system. The whole process is carried out under nitrogen protection.
[0161] Then, another peristaltic pump is used to slowly drip the potassium persulfate solution into the reactor, the dripping speed is also controlled at 4-6 L / min, and the dripping time is 15-20 minutes. The whole process is carried out under nitrogen protection.
[0162] After the initiator is added dropwise, the temperature of the reactor is maintained at 60-80°C, and the reaction is stirred for 4-6 hours to allow the grafting reaction to proceed fully. The stirring speed is maintained at 300-400rpm during the reaction. The entire process is carried out under nitrogen protection.
[0163] (III) Post-processing 1. Product separation After the grafting reaction is completed, the reaction product in the reactor is transferred to a centrifuge and centrifuged at 3000-5000rpm for 10-15 minutes to separate the solid (grafted product) from the liquid (unreacted monomer, initiator, etc.). The upper clear liquid is discarded and the solid product at the lower layer is collected.
[0164] 2. Washing The collected solid product is added to 400L of deionized water and stirred in a reactor for 30-45 minutes at a stirring speed of 200-300rpm. The purpose of this step is to wash away impurities such as residual monomers and initiators.
[0165] Transfer the reaction product to the centrifuge again and centrifuge at 3000 - 5000 rpm for 10 - 15 minutes, discard the upper layer of water; repeat the washing step 2 times to ensure that impurities are washed away.
[0166] 3. Drying The washed solid product is placed in a vacuum drying oven, the temperature is set to 50-60°C, the vacuum degree is -0.08-0.1MPa, and the drying time is 24-48 hours until the product has a constant weight, thereby obtaining the final corn starch compatibilizer product.
[0167] Example 2: Preparation of polylactic acid PLA compatibilizer: The polylactic acid PLA compatibilizer of the present invention is achieved by the following process: 1. Raw material formula (by weight percentage) 1. Polylactic acid PLA: 200kg (molecular weight 100000-500000, model 4032D produced by NatureWorks, USA, as the basic material of the main chain structure) 2. Hydroxypropyl acrylate (monomer): 30kg The double bonds in hydroxypropyl acrylate can react with the main chain of polylactic acid to form side chains under the action of an initiator, and its hydroxypropyl group helps to improve the compatibility with other substances.
[0168] 3. Ethyl lactate (monomer): 30Kg Similar to the structure of polylactic acid, side chains are introduced into the main chain through reactions such as ester exchange, while enhancing the overall compatibility.
[0169] 4. Potassium persulfate (initiator): 3Kg The free radicals generated by the decomposition of potassium persulfate can initiate the reaction between the monomer and the main chain of polylactic acid.
[0170] 5. Ethyl acetate (solvent): 400L It can effectively dissolve polylactic acid and allow the reaction to proceed in a homogeneous system.
[0171] 6. Propylene glycol (auxiliary agent): 30kg As a solvent and auxiliary agent, it adjusts the polarity and reactivity of the reaction system, promotes the reaction and helps to improve compatibility.
[0172] Process steps 1. Raw material pretreatment 1. Polylactic acid dissolution 200 kg of polylactic acid was added to a reaction vessel (1000 L multifunctional reactor with condenser and nitrogen protection device) containing 400 L of ethyl acetate, and stirred to dissolve at room temperature. The stirring speed was set to 200 - 300 rpm until the polylactic acid was completely dissolved to form a transparent solution, which could take 1 - 2 hours.
[0173] 2. Mixing of monomers and additives In another container, 30 Kg of hydroxypropyl acrylate, 30 Kg of ethyl lactate and 30 Kg of propylene glycol were mixed evenly to form a mixed solution for use.
[0174] (II) Triggering reaction 1. Preparation of initiator solution Dissolve 3 kg of potassium persulfate in 20 L of distilled water to prepare an initiator solution.
[0175] 2. Grafting reaction Heat the reaction vessel (containing the ethyl acetate solution of polylactic acid) to 60-70°C, then slowly drip the mixture of monomer and additive into the reaction vessel using a peristaltic pump. The dripping time is controlled within 30-45 minutes, and the stirring speed is maintained at 300-400rpm during the dripping process. The whole process is carried out under nitrogen protection.
[0176] After the addition is completed, continue stirring for 10-15 minutes, and then slowly add the initiator solution to the reaction vessel using a peristaltic pump for 15-20 minutes. The entire process is carried out under nitrogen protection.
[0177] After the initiator is added, the reaction is continued at 60-70°C for 3-5 hours to allow the monomer to fully react with the main chain of polylactic acid and introduce a branched structure into the polylactic acid. The reaction is always under nitrogen protection.
[0178] (III) Post-processing 1. Solvent Removal After the reaction is completed, the reaction mixture is transferred to a distillation apparatus, which is slowly heated to control the temperature at 40-50° C. to distill off the ethyl acetate solvent to obtain a preliminary product.
[0179] 2. Product Purification The preliminary product was washed twice with an appropriate amount of ethanol to remove unreacted monomers and additives, and then dried in a vacuum drying oven at 40-50°C for 24-48 hours until the product had a constant weight to obtain the final polylactic acid (PLA) compatibilizer product.
[0180] Example 3: Making corn starch children's shovel toy 1. Raw material preparation Corn starch: 100 kg of corn starch with a purity of 98% was selected and dried in an air flow dryer according to the above pretreatment method at a temperature of 55°C and an air flow velocity of 2.0 m / s for 4 hours to reduce the moisture content to less than 1%. Then it was placed in a planetary ball mill and ball milled at a speed of 400 r / min for 1 hour. The corn starch after ball milling was screened through a vibrating screen with particles of 80-200 mesh.
[0181] Polylactic acid: 50 kg of polylactic acid PLA with a molecular weight of 100,000-500,000 and model 4032D produced by NatureWorks of the United States was selected. The polylactic acid was crushed into 1-2 mm small particles by a double-roll crusher and dried in a vacuum drying oven at a temperature of 70°C and a vacuum degree of -0.08 MPa for 3.5 hours.
[0182] 2. Mixing process By corn starch 68kg, corn starch compatibilizer 10kg (embodiment 1 product), polylactic acid PLA 10kg, polylactic acid PLA compatibilizer 12kg (embodiment 2 product), nucleating agent polylactic acid stereocomplex 1.5kg, antioxidant ascorbic acid vitamin C 0.6kg, antistatic agent propylene glycol block polyether L64 model 1kg and coloring agent plant pigment corn yellow 1.1kg, according to weight percentage, put into high-speed mixer, high-speed mixer stirring paddle speed is set to 900r / min, mixing time is 22 minutes, and nitrogen flow rate is 7L / min.After mixing, premix is put into twin-screw extruder, screw aspect ratio is 40:1, screw speed is 160r / min, and extruder temperature is set to 110 ℃, 130 ℃, 175 ℃, 170 ℃, 160 ℃ 5, 165 ℃ successively from feeding section to die section.
[0183] 3. Molding process The extruded composite material is directly transported to the barrel of the injection molding machine through a constant temperature pipeline. The injection molding pressure of the injection molding machine is 10MPa, the injection molding temperature is 180℃, and the holding time is 8 seconds. The plastic building block toy mold is used for injection molding, and the water temperature of the mold cooling system is 15℃.
[0184] 4. Post-processing process Annealing treatment: put the formed shovel toy into an annealing furnace, the annealing temperature is 80°C, and the annealing time is 3 hours.
[0185] Surface treatment: Soak the shovel toy in a natural plant rice bran wax solution with a temperature of 70°C and a concentration of 8% for 2 minutes, then take it out and dry it.
[0186] Example 4: Making corn starch children's yellow duck toy 1. Raw material preparation Corn starch: 100kg corn starch with a purity of 98% was selected and dried in an air flow dryer at a temperature of 55°C and an air flow velocity of 2.0m / s for 4 hours until the moisture content dropped to less than 1%. The corn starch was placed in a planetary ball mill and ball milled at a speed of 350r / min for 1.5 hours. The corn starch after ball milling was screened through a vibrating screen with particles of 80-200 mesh.
[0187] Polylactic acid: 50 kg of polylactic acid PLA with a molecular weight of 100,000-500,000 and model 4032D produced by NatureWorks of the United States was selected. The polylactic acid was crushed into smaller particles of 1-2 mm by a double-roll crusher and dried in a vacuum drying oven at a temperature of 80°C and a vacuum degree of -0.08 MPa for 5 hours.
[0188] 2. Mixing process Corn starch 65kg, corn starch compatibilizer 10kg (embodiment 1 product), polylactic acid PLA 10kg, polylactic acid PLA compatibilizer 15kg (embodiment 2 product), nucleating agent polylactic acid stereocomplex 1.5kg, antioxidant ascorbic acid vitamin C 0.5kg, antistatic agent propylene glycol block polyether L64 model 0.9kg and coloring agent plant curcumin 2kg, according to weight percentage, put into high-speed mixer, high-speed mixer stirring paddle speed is set to 950r / min, mixing time is 20 minutes, nitrogen flow rate is 7L / min. After mixing, premix is put into twin-screw extruder, screw aspect ratio is 40:1, screw speed is 160r / min, and extruder temperature is set to 115°C, 130°C, 175°C, 170°C, 160°C, 165°C from feeding section to die section.
[0189] 3. Molding process The extruded composite material is directly transported to the blow molding machine through a constant temperature pipe and blow-molded using a children's yellow duck mold. The blow molding temperature is 175°C, the blowing pressure is 0.4MPa, and the blowing time is between 6 seconds. The cooling method is air cooling, and the fan blows air to the toy to cool it quickly.
[0190] 4. Post-processing process Annealing treatment: annealing temperature is 75°C and annealing time is 2 hours.
[0191] Surface treatment: Soak in 5% rice bran wax solution at 60°C for 3 minutes and then dry.
[0192] After drying, the little yellow duck is painted with organic water-based paint, giving it an orange beak and black and white eyes, making the little yellow duck toy more vivid and cute.
[0193] Example 5: Making wheat starch children's shovel toy 1. Raw material preparation Wheat starch: 100 kg of wheat starch with a purity of 97% was selected. According to the above pretreatment method, the temperature was set at 53°C and the air flow rate was 2.2 m / s in an air flow dryer for 4.5 hours to reduce the moisture content to less than 1. Then it was put into a planetary ball mill and ball milled at a speed of 350 r / min for 1.5 hours. The potato starch after ball milling was screened through a vibrating screen with particles of 120-250 mesh.
[0194] Polylactic acid: 50 kg of polylactic acid PLA with a molecular weight of 100,000-500,000 and model 4032D produced by NatureWorks of the United States was selected. The polylactic acid was crushed into smaller particles of 1-2 mm by a double-roll crusher and dried in a vacuum drying oven at a temperature of 65°C and a vacuum degree of -0.08 MPa for 4 hours.
[0195] 2. Mixing process Wheat starch 62kg, corn starch compatibilizer 14kg (embodiment 1 product), polylactic acid PLA 10kg, polylactic acid PLA compatibilizer 14kg (embodiment 2 product), nucleating agent polylactic acid stereocomplex 1.5kg, antioxidant ascorbic acid vitamin C 0.8kg, antistatic agent propylene glycol block polyether L64 model 1kg and colorant organic pigment phthalocyanine blue 1.1kg, according to weight percentage, put into high-speed mixer, high-speed mixer stirring paddle speed is set to 900r / min, mixing time is 22 minutes, and nitrogen flow rate is 7L / min. After mixing, premix is put into twin-screw extruder, screw aspect ratio is 40:1, screw speed is 160r / min, and extruder temperature is set to 120℃, 135℃, 175℃, 170℃, 160℃5, 165℃ from feeding section to die section.
[0196] 3. Molding process The extruded composite material is directly transported to the barrel of the injection molding machine through a constant temperature pipeline. The injection molding pressure of the injection molding machine is 10MPa, the injection molding temperature is 180℃, and the holding time is 8 seconds. A plastic shovel toy mold is used for injection molding, and the water temperature of the mold cooling system is 15℃.
[0197] Example 6: Making wheat starch children's yellow duck toy 1. Raw material preparation Wheat starch: 100kg of wheat starch with a purity of 97% was selected and dried in an air flow dryer at a temperature of 55°C and an air flow velocity of 1.5m / s for 5 hours until the moisture content dropped to less than 1%. The starch was put into a planetary ball mill and ball milled at a speed of 350r / min for 1.5 hours. The wheat starch after ball milling was screened through a vibrating screen with particles of 120-250 mesh.
[0198] Polylactic acid: 50 kg of polylactic acid PLA with a molecular weight of 100,000-500,000 and model 4032D produced by NatureWorks of the United States was selected. The polylactic acid was crushed into smaller particles of 1-2 mm by a double-roll crusher and dried in a vacuum drying oven at a temperature of 70°C and a vacuum degree of -0.08 MPa for 4 hours.
[0199] 2. Mixing process Wheat starch 60kg, corn starch compatibilizer 15kg (embodiment 1 product), polylactic acid PLA 10kg, polylactic acid PLA compatibilizer 15kg (embodiment 2 product), nucleating agent polylactic acid stereocomplex 1.5kg, antioxidant ascorbic acid vitamin C 0.8kg, antistatic agent propylene glycol block polyether L64 model 1kg and colorant organic pigment lemon yellow 1kg, according to weight percentage, put into high-speed mixer, high-speed mixer stirring paddle speed is set to 1000r / min, mixing time is 15 minutes, nitrogen flow rate is 8L / min. After mixing, premix is put into twin-screw extruder, screw aspect ratio is 40: 1, screw speed is 180r / min, and extruder temperature is set to 115°C, 130°C, 175°C, 170°C, 160°C, 165°C from feeding section to die section.
[0200] 3. Molding process The extruded composite material is directly transported to the blow molding machine through a constant temperature pipe and blow-molded using a children's yellow duck mold. The blow molding temperature is 180°C, the blowing pressure is 0.4MPa, and the blowing time is 7 seconds. The cooling method is air cooling, and the fan blows air to the toy to cool it quickly.
[0201] 4. Post-processing process Annealing treatment: annealing temperature is 75°C and annealing time is 2 hours.
[0202] Surface treatment: Soak in 5% rice bran wax solution at 60°C for 3 minutes and then dry.
[0203] After drying, the little yellow duck is painted with organic water-based paint, giving it an orange beak and black and white eyes, making the little yellow duck toy more vivid and cute.
[0204] Embodiment 7: manufacture potato starch children's shovel toy 1. Raw material preparation Potato starch: 100 kg of potato starch with a purity of 95% was selected. According to the above pretreatment method, it was dried in an air flow dryer at a temperature of 55°C and an air flow velocity of 2.0 m / s for 3.5 hours to reduce the moisture content to less than 1%. Then it was put into a planetary ball mill and ball milled at a speed of 400 r / min for 1 hour. The potato starch after ball milling was screened through a vibrating screen with a particle size of 150-220 mesh.
[0205] Polylactic acid: 50 kg of polylactic acid PLA with a molecular weight of 100,000-500,000 and model 4032D produced by NatureWorks of the United States was selected. The polylactic acid was crushed into smaller particles of 1-2 mm by a double-roll crusher and dried in a vacuum drying oven at a temperature of 65°C and a vacuum degree of -0.08 MPa for 4 hours.
[0206] 2. Mixing process 70 kg of potato starch (because potato starch has good gelatinization and strong viscosity, molecular chain network structure, it can account for more percentages), 10 kg of corn starch compatibilizer (product of Example 1), 10 kg of polylactic acid PLA, 10 kg of polylactic acid PLA compatibilizer (product of Example 2), 1.5 kg of polylactic acid stereocomplex as a nucleating agent, 0.8 kg of ascorbic acid vitamin C as an antioxidant, 1 kg of propylene glycol block polyether L64 model as an antistatic agent, and 1.5 kg of chlorophyll as a colorant are put into a high-speed mixer according to weight percentage. The speed of the stirring paddle of the high-speed mixer is set to 950 r / min, the mixing time is 20 minutes, and the nitrogen flow rate is 7 L / min. After mixing, the premix was placed in a twin-screw extruder with a screw length-to-diameter ratio of 40:1 and a screw speed of 160 r / min. The extruder temperature was set to 110°C, 135°C, 175°C, 170°C, 160°C5, and 165°C from the feeding section to the die section.
[0207] 3. Molding process The extruded composite material is directly transported to the barrel of the injection molding machine through a constant temperature pipeline. The injection molding pressure of the injection molding machine is 10MPa, the injection molding temperature is 180℃, and the holding time is 8 seconds. A plastic shovel toy mold is used for injection molding, and the water temperature of the mold cooling system is 15℃.
[0208] 4. Post-processing process Annealing treatment: put the formed shovel toy into an annealing furnace, the annealing temperature is 80°C, and the annealing time is 2 hours.
[0209] Surface treatment: Soak the shovel toy in a natural plant rice bran wax solution with a temperature of 70°C and a concentration of 8% for 2 minutes, then take it out and dry it.
[0210] Example 8: Making potato starch children's yellow duck toys 1. Raw material preparation Potato starch: 100kg of potato starch with a purity of 96% was selected and dried in an air flow dryer at a temperature of 55°C and an air flow velocity of 1.5m / s for 4 hours until the moisture content dropped to less than 1%. The potato starch was put into a planetary ball mill and ball milled at a speed of 400r / min for 2 hours. The potato starch after ball milling was screened through a vibrating screen with a particle size of 150-220 mesh.
[0211] Polylactic acid: 50 kg of polylactic acid PLA with a molecular weight of 100,000-500,000 and model 4032D produced by NatureWorks of the United States was selected. The polylactic acid was crushed into smaller particles of 1-2 mm by a double-roll crusher and dried in a vacuum drying oven at a temperature of 70°C and a vacuum degree of -0.08 MPa for 4 hours.
[0212] 2. Mixing process 68kg of potato starch (because potato starch has good gelatinization and strong viscosity, molecular chain network structure, it can account for more percentages), 10kg of corn starch compatibilizer (product of Example 1), 10kg of polylactic acid PLA, 15kg of polylactic acid PLA compatibilizer (product of Example 2), 1.5kg of polylactic acid stereocomplex as a nucleating agent, 0.8kg of ascorbic acid vitamin C as an antioxidant, 1kg of propylene glycol block polyether L64 model as an antistatic agent, and 1kg of lemon yellow as a colorant organic pigment are put into a high-speed mixer according to weight percentage. The speed of the stirring paddle of the high-speed mixer is set to 1000r / min, the mixing time is 15 minutes, and the nitrogen flow rate is 9L / min. After mixing, the premix was placed in a twin-screw extruder with a screw length-to-diameter ratio of 40:1 and a screw speed of 160 r / min. The extruder temperature was set to 115°C, 130°C, 175°C, 170°C, 160°C, and 165°C from the feeding section to the die section.
[0213] 3. Molding process The extruded composite material is directly transported to the blow molding machine through a constant temperature pipe and blow-molded using a children's yellow duck mold. The blow molding temperature is 175°C, the blowing pressure is 0.4MPa, and the blowing time is between 6 seconds. The cooling method is air cooling, and the fan blows air to the toy to cool it quickly.
[0214] 4. Post-processing process Annealing treatment: annealing temperature is 75°C and annealing time is 2 hours.
[0215] Surface treatment: Soak in 5% rice bran wax solution at 60°C for 3 minutes and then dry.
[0216] After drying, the little yellow duck is painted with organic water-based paint, giving it an orange beak and black and white eyes, making the little yellow duck toy more vivid and cute.
[0217] Embodiment 9: manufacture rice starch children's shovel toy 1. Raw material preparation Rice starch: 100 kg of rice starch with a purity of 97% was selected and dried in an air flow dryer according to the above pretreatment method at a temperature of 60°C and an air flow velocity of 2.0 m / s for 4.5 hours to reduce the moisture content to less than 1%. Then the rice starch was placed in a planetary ball mill and ball milled at a speed of 400 r / min for 1.5 hours. The rice starch after ball milling was screened through a vibrating screen with a particle size of 180-250 mesh.
[0218] Polylactic acid: 50 kg of polylactic acid PLA with a molecular weight of 100,000-500,000 and model 4032D produced by NatureWorks of the United States was selected. The polylactic acid was crushed into smaller particles of 1-2 mm by a double-roll crusher and dried in a vacuum drying oven at a temperature of 65°C and a vacuum degree of -0.08 MPa for 4 hours.
[0219] 2. Mixing process 55 kg of rice starch (since the amylose and crystallinity of rice starch vary due to different rice varieties, the percentage should be less), 15 kg of corn starch compatibilizer (product of Example 1), 15 kg of polylactic acid PLA, 15 kg of polylactic acid PLA compatibilizer (product of Example 2), 1.5 kg of polylactic acid stereocomplex, 0.8 kg of antioxidant ascorbic acid vitamin C, 1 kg of antistatic agent propylene glycol block polyether L64 model, and 1.5 kg of colorant plant pigment strawberry red pigment are put into a high-speed mixer according to weight percentage, and the speed of the stirring paddle of the high-speed mixer is set to 1000 r / min, the mixing time is 20 minutes, and the nitrogen flow rate is 8 L / min. After mixing, the premix was placed in a twin-screw extruder with a screw length-to-diameter ratio of 40:1 and a screw speed of 180 r / min. The extruder temperature was set to 120°C, 130°C, 175°C, 170°C, 160°C5, and 165°C from the feeding section to the die section.
[0220] 3. Molding process The extruded composite material is directly transported to the barrel of the injection molding machine through a constant temperature pipeline. The injection molding pressure of the injection molding machine is 11MPa, the injection molding temperature is 180℃, and the holding time is 8 seconds. A plastic shovel toy mold is used for injection molding, and the water temperature of the mold cooling system is 15℃.
[0221] 4. Post-processing process Annealing treatment: put the formed shovel toy into an annealing furnace, the annealing temperature is 80°C, and the annealing time is 2 hours.
[0222] Surface treatment: Soak the shovel toy in a natural plant rice bran wax solution with a temperature of 70°C and a concentration of 8% for 2 minutes, then take it out and dry it.
[0223] Example 10: Making a Rice Starch Children's Yellow Duck Toy 1. Raw material preparation Rice starch: 100 kg of rice starch with a purity of 97% was selected and dried in an air flow dryer at a temperature of 65°C and an air flow velocity of 2.0 m / s for 4 hours until the moisture content dropped to less than 1%. The rice starch was put into a planetary ball mill and ball milled at a speed of 400 r / min for 1.5 hours. The rice starch after ball milling was screened through a vibrating screen with particles of 180-250 mesh.
[0224] Polylactic acid: 50 kg of polylactic acid PLA with a molecular weight of 100,000-500,000 and model 4032D produced by NatureWorks Company of the United States was selected. The polylactic acid was crushed into smaller particles of 1-2 mm by a double-roll crusher and dried in a vacuum drying oven at a temperature of 70°C and a vacuum degree of -0.08 MPa for 4 hours.
[0225] 2. Mixing process 55 kg of rice starch (since the amylose and crystallinity of rice starch vary due to different rice varieties, the percentage should be less), 15 kg of corn starch compatibilizer (product of Example 1), 15 kg of polylactic acid PLA, 15 kg of polylactic acid PLA compatibilizer (product of Example 2), 1.5 kg of polylactic acid stereocomplex, 0.8 kg of antioxidant ascorbic acid vitamin C, 1 kg of antistatic agent propylene glycol block polyether L64 model, and 1 kg of colorant organic pigment lemon yellow are put into a high-speed mixer according to weight percentage, and the speed of the stirring paddle of the high-speed mixer is set to 1000 r / min, the mixing time is 20 minutes, and the nitrogen flow rate is 9 L / min. After mixing, the premix was placed in a twin-screw extruder with a screw length-to-diameter ratio of 40:1 and a screw speed of 180 r / min. The extruder temperature was set to 115°C, 130°C, 175°C, 170°C, 160°C5, and 165°C from the feeding section to the die section.
[0226] 3. Molding process The extruded composite material is directly transported to the blow molding machine through a constant temperature pipe and blow-molded using a children's yellow duck mold. The blow molding temperature is 185°C, the blowing pressure is 0.4MPa, and the blowing time is between 6 seconds. The cooling method is air cooling, and the fan blows air to the toy to cool it quickly.
[0227] 4. Post-processing process Annealing treatment: annealing temperature is 75°C and annealing time is 2 hours.
[0228] Surface treatment: Soak in 5% rice bran wax solution at 60°C for 3 minutes and then dry.
[0229] After drying, the little yellow duck is painted with organic water-based paint, giving it an orange beak and black and white eyes, making the little yellow duck toy more vivid and cute.
[0230] Example 11: Making Cassava Starch Children's Shovel Toy 1. Raw material preparation Cassava starch: 100 kg of 95% pure cassava starch was selected and dried in an airflow dryer according to the above pretreatment method at a temperature of 65°C and an airflow velocity of 2.0 m / s for 4 hours to reduce the moisture content to less than 1%. Then the cassava starch was placed in a planetary ball mill and ball-milled at a speed of 450 r / min for 1.5 hours. The ball-milled cassava starch was screened through a vibrating screen with a particle size of 150-220 mesh.
[0231] Polylactic acid: 50 kg of polylactic acid PLA with a molecular weight of 100,000-500,000 and model 4032D produced by NatureWorks of the United States was selected. The polylactic acid was crushed into smaller particles of 1-2 mm by a double-roll crusher and dried in a vacuum drying oven at a temperature of 65°C and a vacuum degree of -0.08 MPa for 4 hours.
[0232] 2. Mixing process 63kg of cassava starch, 14kg of corn starch compatibilizer (product of embodiment 1), 11kg of polylactic acid PLA, 12kg of polylactic acid PLA compatibilizer (product of embodiment 2), 1.5kg of polylactic acid stereocomplex of nucleating agent, 0.8kg of ascorbic acid vitamin C of antioxidant, 1kg of propylene glycol block polyether L64 model of antistatic agent and 1.5kg of lycopene of coloring agent plant pigment are put into high-speed mixer according to weight percentage, and the stirring blade speed of high-speed mixer is set to 900r / min, and the mixing time is 20 minutes, and the nitrogen flow rate is 6L / min. After mixing, the premix is put into a twin-screw extruder, and the screw aspect ratio is 40:1, and the screw speed is 170r / min, and the extruder temperature is set to 110°C, 135°C, 175°C, 170°C, 160°C5, and 165°C from the feeding section to the die section.
[0233] 3. Molding process The extruded composite material is directly transported to the barrel of the injection molding machine through a constant temperature pipeline. The injection molding pressure of the injection molding machine is 10MPa, the injection molding temperature is 180℃, and the holding time is 8 seconds. A plastic shovel toy mold is used for injection molding, and the water temperature of the mold cooling system is 15℃.
[0234] Post-processing Annealing treatment: put the formed shovel toy into an annealing furnace, the annealing temperature is 80°C, and the annealing time is 3 hours.
[0235] Surface treatment: Soak the shovel toy in a natural plant rice bran wax solution with a temperature of 70°C and a concentration of 8% for 2 minutes, then take it out and dry it.
[0236] Example 12: Making cassava starch children's yellow duck toys 1. Raw material preparation Cassava starch: 100 kg of cassava starch with a purity of 95% was selected and dried in an air flow dryer at a temperature of 65°C and an air flow velocity of 2.5 m / s for 3 hours until the moisture content dropped to less than 1%. The starch was put into a planetary ball mill and ball milled at a speed of 450 r / min for 1.5 hours. The rice starch after ball milling was screened through a vibrating screen with a particle size of 150-220 mesh.
[0237] Polylactic acid: 50 kg of polylactic acid PLA with a molecular weight of 100,000-500,000 and model 4032D produced by NatureWorks of the United States was selected. The polylactic acid was crushed into smaller particles of 1-2 mm by a double-roll crusher and dried in a vacuum drying oven at a temperature of 70°C and a vacuum degree of -0.08 MPa for 4 hours.
[0238] 2. Mixing process 60kg of cassava starch, 15kg of corn starch compatibilizer (product of embodiment 1), 12kg of polylactic acid PLA, 13kg of polylactic acid PLA compatibilizer (product of embodiment 2), 1.5kg of nucleating agent polylactic acid stereocomplex, 0.8kg of antioxidant ascorbic acid vitamin C, 1kg of antistatic agent propylene glycol block polyether L64 model and 1kg of colorant organic pigment lemon yellow are put into a high-speed mixer according to weight percentage, and the high-speed mixer stirring paddle speed is set to 900r / min, and the mixing time is 20 minutes, and the nitrogen flow rate is 9L / min. After mixing, the premix is put into a twin-screw extruder, and the screw aspect ratio is 40:1, and the screw speed is 170r / min, and the extruder temperature is set to 115°C, 130°C, 175°C, 170°C, 160°C, and 165°C from the feeding section to the die section.
[0239] 3. Molding process The extruded composite material is directly transported to the blow molding machine through a constant temperature pipe and blow-molded using a children's yellow duck mold. The blow molding temperature is 175°C, the blowing pressure is 0.4MPa, and the blowing time is 8 seconds. The cooling method is air cooling, and the fan blows air to the toy to cool it quickly.
[0240] 4. Post-processing process Annealing treatment: annealing temperature is 75°C and annealing time is 2 hours.
[0241] Surface treatment: Soak in 5% rice bran wax solution at 60°C for 3 minutes and then dry.
[0242] After drying, the little yellow duck is painted with organic water-based paint, giving it an orange beak and black and white eyes, making the little yellow duck toy more vivid and cute.
[0243] According to the four parts of the national standard for children's toys GB6675-2014, the children's toy shovel products of the embodiment are subject to the company's own quality control test: 1. GB6675.1-2014 "Safety of Toys Part 1: Basic Specifications": Safety requirements: Toys and materials designed for children to play with must not cause any harm to children. Toys must be manufactured without sharp edges, small parts that may cause choking, and should not contain harmful substances.
[0244] Specific safety requirements: Limit requirements for plasticizers.
[0245] The plasticizer content of the children's toy shovel in the embodiment is detected by gas chromatography-mass spectrometry (GC-MS): 2. GB6675.2-2014 "Toy Safety Part 2: Mechanical and Physical Properties": Material requirements: Visually inspect the toys and all materials used in the toys to ensure they are clean and free from contamination.
[0246] Small Parts Policy: Children's toys must not contain small parts and should not have sharp edges before and after abuse testing.
[0247] Protrusion requirements: Rigid parts on toys should not pose a puncture hazard before or after abuse testing.
[0248] Children's toy shovel abuse test of the embodiment: 3. GB6675.3-2014 "Safety of Toys Part 3: Flammability": This plant starch composite material is not a flammable material, and the children's toy shovel made from it does not pose a flammable risk and does not require a flammability test.
[0249] GB6675.4-2014 "Safety of Toys Part 4: Migration of Certain Elements": The surface of the children's toy shovel in the embodiment is not painted, and therefore does not need to be tested for heavy metals in the migratable elements.
[0250] According to the four parts of the national standard for children's toys GB6675-2014, the company conducted its own quality control test on the children's toy yellow duck product in the embodiment: 1. GB6675.1-2014 "Safety of Toys Part 1: Basic Specifications": Safety requirements: Toys and materials designed for children to play with must not cause any harm to children. Toys must be manufactured without sharp edges, small parts that may cause choking, and should not contain harmful substances.
[0251] Specific safety requirements: Limit requirements for plasticizers.
[0252] The plasticizer content of the children's toy yellow duck in the embodiment is detected by gas chromatography-mass spectrometry (GC-MS): 2. GB6675.2-2014 "Toy Safety Part 2: Mechanical and Physical Properties": Material requirements: Visually inspect the toys and all materials used in the toys to ensure they are clean and free from contamination.
[0253] Small Parts Policy: Children's toys must not contain small parts and should not have sharp edges before and after abuse testing.
[0254] Protrusion requirements: Rigid parts on toys should not pose a puncture hazard before or after abuse testing.
[0255] Children's toy yellow duck abuse test of the embodiment: 3. GB6675.3-2014 "Safety of Toys Part 3: Flammability": This plant starch composite material is not a flammable material, and the children's yellow duck toy made from it does not pose a flammability risk and does not require flammability testing.
[0256] 4. GB6675.4-2014 "Safety of Toys Part 4: Migration of Certain Elements": The heavy metal test of the migratable elements in the children's toy yellow duck in the embodiment is to detect the orange pigment in the yellow duck's mouth, and the detection method is inductively coupled plasma atomic emission spectrometry (ICP-AES) The heavy metal test of the migratable elements in the children's toy yellow duck in the embodiment is to detect the black pigment in the eyes of the yellow duck, and the detection method is inductively coupled plasma atomic emission spectrometry (ICP-AES) The heavy metal test of the migratable elements in the children's toy yellow duck in the embodiment is to detect the white pigment in the eyes of the yellow duck, and the detection method is inductively coupled plasma atomic emission spectrometry (ICP-AES) This time, a small shovel toy and a small yellow duck toy made of plant starch thermoplastic composite materials were tested. After injection molding and blow molding, the two toys passed the first, second, third and fourth parts of the national children's toy standard GB6675-2014.
[0257] The above specific implementation methods are only preferred embodiments of the present invention, and are used to illustrate the technical solutions of the present invention, but are not used to limit the present invention. The innovation of the present invention lies in the uniqueness of using plant starch as a material for manufacturing toys, which is safe, environmentally friendly and biodegradable, and can replace traditional petroleum-based plastic toys. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of this invention. In summary, the content of this specification should not be understood as a limitation of the present invention.
Claims
1. A material for making children's toys using plant starch, characterized in that: The formula materials mainly include the following raw material components by weight percentage: 55-70% plant starch, 10-18% corn starch compatibilizer, 10-12% polylactic acid PLA, 10-15% polylactic acid PLA compatibilizer, 1-2% nucleating agent, 0.1-1% antioxidant, 0.5-2% antistatic agent, and 1-2% colorant; The plant starch is one or a mixture of corn starch, wheat starch, potato starch, rice starch and tapioca starch; The relative molecular weight range of the polylactic acid PLA is 1x10 5 -5x10 5 between; The nucleating agent is a polylactic acid stereocomplex SC, a polylactic acid PLLA / polylactic acid PDLA stereomer; The antioxidant is ascorbic acid vitamin C; The antistatic agent is a polyether antistatic agent, propylene glycol block polyether L64; The colorant is an organic colorant or a plant pigment. The organic pigment is one or more of phthalocyanine blue, phthalocyanine green, lemon yellow pigment, and pigment red 254. The plant pigment is one or more of zeaxanthin, curcumin, strawberry red pigment, and lycopene pigment.
2. The material for making children's toys from plant starch according to claim 1, characterized in that: The corn starch compatibilizer is prepared by modified grafting of the reducing end of the terminal group of corn starch molecular chain, and its raw material formula includes by weight percentage: 10kg corn starch, 0.5-1.0kg ascorbic acid vitamin C reducing agent, 2-5kg hydroxyethyl methacrylate monomer, 1-4kg itaconic acid monomer, and 0.1-0.5kg potassium persulfate initiator.
3. The material for making children's toys from plant starch according to claim 1, characterized in that: The corn starch compatibilizer process steps are: (I) Reduction pretreatment of corn starch: (1) solution preparation, (2) reduction reaction; (ii) Grafting reaction: (1) preparing a monomer mixture, (2) preparing an initiator solution, (3) grafting copolymerization reaction; (iii) Post-processing: (1) product separation, (2) washing, and (3) drying.
4. The material for making children's toys from plant starch according to claim 1, characterized in that: The PLA compatibilizer has a raw material formula according to weight percentage: 100g PLA, 10-25g hydroxypropyl acrylate monomer, 10-25g ethyl lactate monomer, 1-5g potassium persulfate initiator, 150-250 mL ethyl acetate solvent, and 10-25g propylene glycol auxiliary agent; PLA molecular weight 1x10 5 -5x10 5 As the basic materials of the main chain structure, hydroxypropyl acrylate monomer and ethyl lactate monomer can also be selected from one or more of hydroxyethyl methacrylate, itaconic acid, acrylic acid, polyethylene glycol, and maleic anhydride; the initiator can be selected from one or more of hydrogen peroxide, ammonium persulfate, lipase, laccase, tea polyphenols, and gallic acid; the solvent can be selected from one or more of ethyl lactate, polyethylene glycol, and propylene glycol; the auxiliary agent can be added according to the product performance requirements, and can be selected from one or more of nucleating agents such as talc powder, amide compounds, chain extenders such as epoxy functionalized chain extenders, and oxazoline type chain extenders; the plasticizer can be selected from one or more of citrate esters, polyethylene glycol, anti-hydrolysis agents such as carbodiimide anti-hydrolysis agents, and coupling agents such as silane coupling agents.
5. The material for making children's toys from plant starch according to claim 4, characterized in that: The prepared polylactic acid PLA compatibilizer has the following process steps: (i) Raw material pretreatment: (1) dissolving polylactic acid, (2) mixing monomers and additives; (ii) Initiation reaction: (1) Preparation of initiator solution, (2) Grafting reaction; (iii) Post-processing: (1) solvent removal, (2) product purification.
6. A method for manufacturing a children's toy made of plant starch, using the plant starch according to any one of claims 1 to 5 to manufacture the children's toy material, characterized in that: The manufacturing process includes the following steps:
1. Raw material preparation: (1) Plant starch raw materials: pre-treat the plant starch by first drying the plant starch in an air flow dryer, then grinding the dried plant starch in a planetary ball mill, and screening the plant starch after grinding to ensure that the particles meet the standards; (2) Polylactic acid raw material: select polylactic acid (PLA) with appropriate molecular weight, pass the polylactic acid through a double-roll crusher, crush it, and then place it in a vacuum drying oven for drying; (II) Mixing process: (1) The pretreated plant starch and polylactic acid (PLA), corn starch compatibilizer, polylactic acid compatibilizer, nucleating agent, antioxidant, antistatic agent, and colorant are placed in a high-speed mixer according to weight percentage and mixed, and nitrogen is introduced into the mixer to prevent the materials from being oxidized during the mixing process; (2) After the mixing is completed, the premix is placed in a twin-screw extruder for blending and extrusion. The feeding section, solid conveying section, melting section, mixing section, exhaust section, and homogenization section of the extruder are set with a temperature gradient to ensure the physical reaction of the plant starch and polylactic acid PLA to be fully blended, forming a composite material extrusion, and directly transporting it to a thermoplastic machine for molding through a constant temperature pipeline, or cooling and pelletizing; (III) Molding process: (1) The extruded composite material is directly transported to the barrel of the injection molding, blow molding, and hot press through a constant temperature pipeline for plasticization, which can reduce the energy consumption of the melting process of the injection molding machine and reduce the change in material properties caused by the secondary melting of the granular material or the re-melting of the granules; (2) Sending the composite material to a molding machine for thermoplastic molding, and using corresponding molds for thermoplastic molding according to the design requirements of different toys; (IV) Post-processing process: (1) Annealing treatment: placing the formed toys into an annealing furnace for annealing treatment; (2) Painting: coating the surface of toys, printing and other decorative treatments on toys; (3) Surface treatment: Use non-toxic, biodegradable natural plant rice bran wax to treat the surface of toys.
7. A method for manufacturing a plant starch children's toy according to claim 6, characterized in that: In the raw material preparation, the plant starch is selected as corn starch, the corn starch is placed in an air flow dryer, and dried for 2-5 hours at a temperature of 50-60°C and an air flow velocity of 1.5-2.5m / s to reduce the moisture content of the corn starch to 0.5%-1%; then, the dried corn starch is placed in a planetary ball mill and ball milled at a speed of 300-500r / min for 0.5-2 hours, and the corn starch after ball milling meets the 80-200 mesh standard after passing through a vibrating screen.
8. The method for manufacturing a plant starch children's toy according to claim 6, characterized in that: In the preparation of raw materials, polylactic acid (PLA) with a suitable molecular weight of 100,000 - 500,000 is selected. Before use, the polylactic acid is crushed into 1-2 mm smaller particles by a double-roll crusher, placed in a vacuum drying oven, and dried for 3 - 5 hours at a temperature of 60 - 80 ° C and a vacuum degree of -0.08 to - 0.1MPa to remove moisture and small molecular impurities.
9. The method for manufacturing a plant starch children's toy according to claim 6, characterized in that: In the mixing process, the stirring paddle speed of the high-speed mixer is set to 800-1200r / min, the mixing time is 10-30 minutes, and during the mixing process, nitrogen is introduced into the mixer with a nitrogen flow rate of 5-10L / min to prevent the material from being oxidized during the mixing process.
10. The method for manufacturing a plant starch children's toy according to claim 6, characterized in that: In the mixing process, the screw aspect ratio of the twin-screw extruder is 30:1 - 52:1, the screw speed is 100 - 200r / min, and the temperature setting of each section of the extruder is: the feeding section needs to have a large conveying capacity to ensure that the material can stably and continuously enter the screw, and the temperature range is set at 100℃-130℃. The solid conveying section compacts the loose powdered material and fills the screw groove to prepare for the melting and plasticization of the material downstream. The temperature range is 120℃-140℃. The exhaust port is set to reduce the gas content in the material. The melting section is the key stage for the material to transform from solid to liquid. Sufficient heat and shear force need to be provided to allow the plant starch and polylactic acid to be completely melted and mixed evenly. The temperature range is set at 150℃-180℃. The mixing section is the stage where corn starch and polylactic acid are fully Mix to form a uniform melt, and further reduce the size of the dispersed phase of the material to improve the mixing effect. The temperature range is 155℃-170℃. The exhaust section is mainly used to discharge moisture, entrained air and volatile components in the material so that the gas can be discharged smoothly. The temperature range is 140℃-160℃. The homogenization section makes the material at the die mouth have a certain density and further mixes it to achieve the purpose of smooth extrusion molding. The temperature range is 150℃-165℃. This temperature gradient setting ensures that the plant starch and polylactic acid PLA are fully blended and appropriate physical and chemical reactions occur to form a uniform composite material. Extrusion, cooling, and hot air drying obtain the plant starch composite material.
Citation Information
Patent Citations
Coupling and capacity increasing technique for coblended interface of biodegradation polylactic acid / starch composite material
CN101367986A
Modified thermoplastic starch and preparation method and application thereof
CN111100245A
Compatibilizer and high-starch-content full-biodegradable film adopting compatibilizer
CN113845621A
Starch modification method and application of starch modification method in degradable plastics
CN114213587A
Biomass full degradable material and its preparation technology
CN1948374A
Cited By
Plant-based degradable foaming material as well as preparation method and application thereof
CN120665448A
Plant-based degradable foamed material and preparation method and application thereof
CN120665448B